Optical film, polarizing plate, surface plate, image display panel and image display device using the same, method for producing and selecting the same, method for evaluating fingerprint wiping properties
By designing a concave and convex shape that meets the specific Sa and Vmp ratio on the first surface of the optical film, the problem of poor fingerprint wipeability of the existing optical film is solved, and high anti-glare properties and good fingerprint wipeability are achieved.
Patent Information
- Application Number
- CN202410375596.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-09-25
AI Technical Summary
The conventional optical film has a concave and convex shape on the surface and an anti-reflective layer is attached, which leads to a reduction in the wiping properties of the fingerprint, affecting aesthetics and stain resistance.
An optical film is designed, with its first surface having a concave and convex shape, which satisfies a specific arithmetic average height Sa and a protruding peak solid volume Vmp ratio, ensuring both anti-glare and fingerprint wipeability.
It achieves the improvement of fingerprint wipeability while maintaining high anti-glare and aesthetics, and ensures excellent performance of the optical film.
Smart Images

Figure CN118033794B_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application with the application date of September 25, 2023, the invention name of "Optical film and polarizing plate, surface plate, image display panel and image display device using the optical film, manufacturing method and selection method of the optical film, and evaluation method of fingerprint wiping properties", and application number 202380013248.9 (PCT / JP2023 / 034628). Technical Field
[0002] The present disclosure relates to an optical film, a polarizing plate, a surface plate, an image display panel, and an image display device using the optical film, as well as a method for producing the optical film, a method for selecting the optical film, and a method for evaluating fingerprint wiping properties. Background Art
[0003] An optical film may be provided on the surface of an image display device such as a display screen of a television, a notebook PC, or a desktop PC in order to suppress reflection of background such as lighting or people or to suppress reflection of the surface.
[0004] As optical films, for example, Patent Documents 1 to 3 have been proposed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2019 / 026466
[0008] Patent Document 2: International Publication No. 2019 / 026471
[0009] Patent Document 3: Japanese Patent Application Publication No. 2019-85473 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The optical films of Patent Documents 1 to 2 are anti-glare films having an anti-glare layer with uneven surfaces. Regarding optical films having uneven surfaces, fingerprints may enter the uneven surfaces, so there is a tendency for fingerprint wipeability to decrease. For anti-glare films, the better the anti-glare properties are, the higher the tendency for fingerprint wipeability to decrease. The optical films of Patent Documents 1 to 2 have not conducted any research on antifouling properties.
[0012] The optical film of Patent Document 3 is a coating film having an oleic acid slide angle of 32° or less. The coating film of Patent Document 3 has the problem of being easy to wipe off fingerprints, but it cannot be said that the fingerprint wiping property is good.
[0013] If fingerprints attached to the optical film are not wiped off sufficiently, the contrast in optical properties between the portion with fingerprint components and the portion without fingerprint components will reduce the aesthetics of the optical film. In particular, in the case of an optical film with an anti-reflection layer, the contrast in reflectivity between the portion with fingerprint components and the portion without fingerprint components becomes large, which greatly reduces the aesthetics of the optical film.
[0014] The problem of the present disclosure is to provide an optical film having excellent anti-glare properties and good fingerprint wiping properties in an optical film having a concavo-convex shape on the surface and an anti-reflection layer on the surface. The problem of the present disclosure is to provide a polarizing plate, a surface plate, an image display panel and an image display device having excellent anti-glare properties and good fingerprint wiping properties. The problem of the present disclosure is to provide a method for manufacturing an optical film having excellent anti-glare properties and good fingerprint wiping properties. The problem of the present disclosure is to provide a method for selecting an optical film having excellent anti-glare properties and good fingerprint wiping properties. The problem of the present disclosure is to provide an evaluation method that can easily evaluate fingerprint wiping properties.
[0015] Means for solving problems
[0016] The present disclosure provides the following [1] to
[15] .
[0017] [1] An optical film comprising a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0018] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0019] The first surface has a concavoconvex shape,
[0020] The arithmetic mean height Sa of the first surface as specified in ISO 25178-2:2012 is 0.05 μm or more,
[0021] The first surface satisfies the following formula 1,
[0022] Sw×Vmp≤2.00(Formula 1),
[0023] In Formula 1, "Sw" is the inclination angle when a 30 μl drop of pure water flows down on the first surface, and in Formula 1, "Vmp" is the value of the protruding peak solid volume of the first surface specified by ISO 25178-2:2012. The unit of the inclination angle is degree, and the unit of the protruding peak solid volume is ml / m 2 .
[0024] [2] A polarizing plate comprising a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein:
[0025] At least one of the first transparent protective plate and the second transparent protective plate is the optical film described in [1], and the second surface of the optical film is arranged to face the polarizer.
[0026] [3] A surface plate for an image display device, which is formed by laminating a protective film to a resin plate or a glass plate, wherein:
[0027] The protective film is the optical film described in [1], and the second surface of the optical film is arranged to face the resin plate or the glass plate.
[0028] [4] An image display panel comprising a display element and an optical film disposed on a light emitting surface side of the display element, wherein the image display panel includes the optical film according to [1] as the optical film.
[0029] [5] An image display device comprising the image display panel described in [4].
[0030] [6] A method for producing an optical film, which is the method for producing an optical film according to [1], wherein:
[0031] The optical film production method includes: a first step of forming an anti-glare layer on a substrate; and a second step of forming an anti-reflection layer on the anti-glare layer.
[0032] [7] A method for selecting an optical film, the method comprising selecting an optical film that satisfies the following selection conditions:
[0033] (Optical film selection conditions)
[0034] The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0035] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0036] The first surface has a concavoconvex shape,
[0037] The arithmetic mean height Sa of the first surface as specified in ISO 25178-2:2012 is 0.05 μm or more,
[0038] The first surface satisfies the following formula 1,
[0039] Sw×Vmp≤2.00(Formula 1),
[0040] In Formula 1, "Sw" is the inclination angle when a 30 μl drop of pure water flows down on the first surface, and in Formula 1, "Vmp" is the value of the protruding peak solid volume of the first surface specified by ISO 25178-2:2012. The unit of the inclination angle is degree, and the unit of the protruding peak solid volume is ml / m 2 .
[0041] [8] An optical film comprising a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0042] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0043] The first surface has a concavoconvex shape,
[0044] The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 above,
[0045] The falling contact angle measured by the following method is 30.0 degrees or more,
[0046] <Measurement of drop contact angle>
[0047] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0048] [9] A polarizing plate comprising a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein:
[0049] At least one of the first transparent protective plate and the second transparent protective plate is the optical film described in [8], and the second surface of the optical film is arranged to face the polarizer.
[0050]
[10] A surface plate for an image display device, which is formed by laminating a protective film on a resin plate or a glass plate, wherein the protective film is the optical film described in [8], and the second surface of the optical film is arranged opposite to the resin plate or the glass plate.
[0051]
[11] An image display panel comprising a display element and an optical film disposed on a light emitting surface side of the display element, wherein the image display panel includes the optical film described in [8] as the optical film.
[0052]
[12] An image display device comprising the image display panel described in
[11] .
[0053]
[13] A method for producing an optical film, which is the method for producing an optical film described in [8], wherein the method for producing an optical film comprises: a first step of forming an anti-glare layer on a substrate; and a second step of forming an anti-reflection layer on the anti-glare layer.
[0054]
[14] A method for selecting an optical film, the method comprising selecting an optical film that satisfies the following selection conditions:
[0055] (Optical film selection conditions)
[0056] The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0057] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0058] The first surface has a concavoconvex shape,
[0059] The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 above,
[0060] The falling contact angle measured by the following method is 30.0 degrees or more,
[0061] <Measurement of drop contact angle>
[0062] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0063]
[15] A method for evaluating fingerprint wiping properties, wherein the value of the falling contact angle measured by the following measurement is used as an evaluation index,
[0064] <Measurement of drop contact angle>
[0065] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the surface of the object to be measured, and the droplet was dropped perpendicularly to the surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0066] Effects of the Invention
[0067] The optical film, polarizing plate, surface plate, image display panel and image display device disclosed in the present invention are excellent in anti-glare properties and can make fingerprint wiping properties good. The manufacturing method of the optical film disclosed in the present invention can easily manufacture an optical film with excellent anti-glare properties and good fingerprint wiping properties. The selection method of the optical film disclosed in the present invention can efficiently select an optical film with excellent anti-glare properties and good fingerprint wiping properties. The evaluation method of fingerprint wiping properties disclosed in the present invention can easily evaluate the fingerprint wiping properties of a measurement object. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is a schematic cross-sectional view showing one embodiment of the optical film of the present disclosure.
[0069] Figure 2 is a cross-sectional view showing one embodiment of the image display panel of the present disclosure.
[0070] Figure 3 This is a diagram for explaining the inclination angle (degrees) of pure water droplets when they flow down.
[0071] Figure 4 This is a schematic cross-sectional view showing one embodiment of the optical film of the present disclosure.
[0072] Figure 5 is a cross-sectional view showing one embodiment of the image display panel of the present disclosure. DETAILED DESCRIPTION
[0073] Hereinafter, embodiments of the present disclosure will be described.
[0074] [Optical film according to the first embodiment]
[0075] The optical film according to the first embodiment of the present disclosure is as follows.
[0076] An optical film having a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0077] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0078] The first surface has a concavoconvex shape,
[0079] The arithmetic mean height Sa of the first surface as specified in ISO 25178-2:2012 is 0.05 μm or more,
[0080] The first surface satisfies the following formula 1,
[0081] Sw×Vmp≤2.00(Formula 1),
[0082] In Formula 1, "Sw" is the inclination angle when a 30 μl drop of pure water flows down on the first surface, and in Formula 1, "Vmp" is the value of the protruding peak solid volume of the first surface specified by ISO 25178-2:2012. The unit of the inclination angle is degree, and the unit of the protruding peak solid volume is ml / m 2 .
[0083] Figure 1 It is a schematic cross-sectional view of the cross-sectional shape of the optical film 100 according to the first embodiment of the present disclosure.
[0084] Figure 1 The optical film 100 has: a first surface having a concavoconvex shape; and a second surface which is a surface opposite to the first surface. Figure 1 In the figure, the upper surface is the first surface, and the lower surface is the second surface.
[0085] Figure 1 The optical film includes an antireflection layer 30, an antiglare layer 20, and a substrate 10 in this order from the first surface toward the second surface.
[0086] Figure 1 That is, the scale of each layer constituting the optical film 100 and the scale of the concavo-convex shape are schematically shown for ease of illustration and are different from the actual scale. Figure 2 and Figure 3 Same.
[0087] The optical film of the first embodiment of the present disclosure is not limited to Figure 1 For example, the optical film of the first embodiment of the present disclosure may also be a laminated structure without a substrate. The optical film of the first embodiment of the present disclosure may also have layers other than the substrate, the anti-glare layer, and the anti-reflection layer.
[0088] <Page 1>
[0089] The optical film according to the first embodiment of the present disclosure has a first surface. In the optical film according to the first embodiment of the present disclosure, it is preferable that the surface of the antireflection layer is the first surface.
[0090] The first surface of the optical film of the first embodiment has a concavo-convex shape, and the arithmetic mean height Sa specified by ISO 25178-2:2012 is 0.05 μm or more. In the case where the first surface does not have a concavo-convex shape, the anti-glare property of the optical film cannot be improved. By making the first surface have a concavo-convex shape and making Sa 0.05 μm or more, the anti-glare property of the optical film can be easily improved.
[0091] The Sa of the first surface in the first embodiment is preferably 0.10 μm or more, more preferably 0.20 μm or more, and further preferably 0.30 μm or more.
[0092] When the Sa of the first surface is too large, the scratch resistance of the optical film may decrease. Therefore, the Sa of the first surface is preferably 0.80 μm or less, more preferably 0.60 μm or less, and further preferably 0.45 μm or less.
[0093] Regarding the implementation methods of the range of Sa of the first surface, there can be listed as 0.05μm or more and 0.80μm or less, 0.05μm or more and 0.60μm or less, 0.05μm or more and 0.45μm or less, 0.10μm or more and 0.80μm or less, 0.10μm or more and 0.60μm or less, 0.10μm or more and 0.45μm or less, 0.20μm or more and 0.80μm or less, 0.20μm or more and 0.60μm or less, 0.20μm or more and 0.45μm or less, 0.30μm or more and 0.80μm or less, 0.30μm or more and 0.60μm or less, 0.30μm or more and 0.45μm or less.
[0094] The first surface of the optical film of the first embodiment satisfies the following formula 1:
[0095] Sw×Vmp≤2.00(Formula 1),
[0096] In Formula 1, "Sw" is the inclination angle (degrees) when a 30 μl drop of pure water flows down on the first surface, and "Vmp" is the protruding peak solid volume (ml / m2) of the first surface as specified in ISO 25178-2:2012. 2 ) value.
[0097] In the first embodiment, the fingerprint wiping property can be easily improved by setting the value of Sw×Vmp of the first surface to 2.00 or more. The relationship between Sw×Vmp and the fingerprint wiping property will be described below.
[0098] Sw is the tilt angle (degrees) when a drop of 30 μl of pure water flows down on the first surface. In this specification, the "tilt angle (degrees) when a drop of 30 μl of pure water flows down" is sometimes referred to as the "pure water falling tilt angle". Fingerprints contain a large amount of water. Therefore, the smaller the Sw of the first surface, the weaker the adhesion between the first surface and the fingerprint, and there is a tendency for fingerprints to be easily removed. However, only reducing the Sw of the first surface sometimes cannot make the fingerprint wiping property good. In particular, in the case of making the anti-glare property of the optical film good, it is difficult to make the fingerprint wiping property good by only reducing the Sw of the first surface.
[0099] Vmp is the volume of the protruding peak (ml / m 2). Vmp is a parameter indicating the volume of a protruding portion that is higher than the core portion. The core portion is equivalent to a portion having an average height in a concave-convex shape. The larger the Vmp, the larger the volume of the portion protruding than the core portion. In this specification, "the portion protruding than the core portion" is sometimes referred to as a "protruding convex portion". Sa and Vmp are not necessarily related, but if Sa is increased in order to achieve good anti-glare properties, there is a tendency for Vmp to become larger. Moreover, when Vmp becomes larger, fingerprints can easily enter between the protruding convex portions, so fingerprint wiping properties are easily reduced. If the Vmp of the first surface is reduced in order to suppress fingerprints from entering between the protruding convex portions, it is difficult to achieve good anti-glare properties for the optical film. In addition, it is difficult to achieve good fingerprint wiping properties for the optical film by only reducing the Vmp of the first surface.
[0100] As described above, it is difficult to make the fingerprint wiping property of the optical film with anti-glare properties good by adjusting only Sw and only Vmp. Therefore, the optical film of the first embodiment of the present disclosure has good fingerprint wiping property by setting Sw×Vmp to less than 2.00. Sw×Vmp being less than 2.00 means that Sw and Vmp are not extremely large, and at least one of Sw and Vmp is small. Therefore, by setting Sw×Vmp to less than 2.00, the fingerprint wiping property of the optical film can be made good.
[0101] In the first embodiment, Sw×Vmp is preferably 1.60 or less, more preferably 1.40 or less, and further preferably 1.20 or less.
[0102] Sw×Vmp is too small, which means that at least one of Sw and Vmp is too small. When Sw is too small, the content of fluorine compounds and organosilicon compounds in the anti-reflection layer increases, and the scratch resistance of the optical film is easily reduced. When Vmp is too small, Sa becomes small, and the anti-glare property is easily reduced. Therefore, Sw×Vmp is preferably 0.15 or more, more preferably 0.25 or more, more preferably 0.40 or more, and more preferably 0.60 or more.
[0103] In the first embodiment, embodiments of the range of Sw×Vmp of the first surface include 0.15 to 2.00, 0.15 to 1.60, 0.15 to 1.40, 0.15 to 1.20, 0.25 to 2.00, 0.25 to 1.60, 0.25 to 1.40, 0.25 to 1.20, 0.40 to 2.00, 0.40 to 1.60, 0.40 to 1.40, 0.40 to 1.20, 0.60 to 2.00, 0.60 to 1.60, 0.60 to 1.40, 0.60 to 1.20.
[0104] In the first embodiment, in order to easily make Sw×Vmp 1.60 or less, Sw of the first surface is preferably 65 (degrees) or less, more preferably 40 (degrees) or less, and further preferably 30 (degrees) or less.
[0105] In the first embodiment, in order to suppress a decrease in the scratch resistance of the optical film, the Sw of the first surface is preferably 10 (degrees) or more, more preferably 13 (degrees) or more, and even more preferably 17 (degrees) or more.
[0106] In the first embodiment, embodiments of the range of Sw of the first surface include greater than 10 degrees and less than 65 degrees, greater than 10 degrees and less than 40 degrees, greater than 10 degrees and less than 30 degrees, greater than 13 degrees and less than 65 degrees, greater than 13 degrees and less than 40 degrees, greater than 13 degrees and less than 30 degrees, greater than 17 degrees and less than 65 degrees, greater than 17 degrees and less than 40 degrees, and greater than 17 degrees and less than 30 degrees.
[0107] In the optical film according to the first embodiment of the present disclosure, the pure water contact angle of the first surface is preferably 100 degrees or more and 120 degrees or less, and more preferably 110 degrees or more and 115 degrees or less.
[0108] In this specification, the pure water contact angle is measured by dropping 1.0 μL of pure water on the surface of the first surface and measuring the static contact angle 10 seconds after the drop of water according to the θ / 2 method.
[0109] In the first embodiment, in order to easily make Sw×Vmp 1.60 or less, the Vmp of the first surface is preferably 0.100 (ml / m 2 ) or less, more preferably 0.080 (ml / m 2 ) or less, more preferably 0.060 (ml / m 2 ) or less, more preferably 0.045 (ml / m 2 )the following.
[0110] In the first embodiment, in order to easily improve the anti-glare property, the Vmp of the first surface is preferably 0.005 (ml / m 2 ) or more, more preferably 0.007 (ml / m 2 ) or more, more preferably 0.010 (ml / m 2 ) or more, more preferably 0.020 (ml / m 2 )above.
[0111] Regarding the embodiment of the range of Vmp of the first surface, 0.005 ml / m 2 Above and 0.100ml / m 2 Below, 0.005ml / m 2 Above and 0.080ml / m2 Below, 0.005ml / m 2 Above and 0.060ml / m 2 Below, 0.005ml / m 2 Above and 0.045ml / m 2 Below, 0.007ml / m 2 Above and 0.100ml / m 2 Below, 0.007ml / m 2 Above and 0.080ml / m 2 Below, 0.007ml / m 2 Above and 0.060ml / m 2 Below, 0.007ml / m 2 Above 0.045ml / m 2 Below, 0.010ml / m 2 Above and 0.100ml / m 2 Below, 0.010ml / m 2 Above and 0.080ml / m 2 Below, 0.010ml / m 2 Above and 0.060ml / m 2 Below, 0.010ml / m 2 Above 0.045ml / m 2 Below, 0.020ml / m 2 Above and 0.100ml / m 2 Below, 0.020ml / m 2 Above and 0.080ml / m 2 Below, 0.020ml / m 2 Above and 0.060ml / m 2 Below, 0.020ml / m 2 Above 0.045ml / m 2 the following.
[0112] The description in this paragraph is common to the first embodiment and the second embodiment.
[0113] In this specification, the "pure water drop inclination angle" of an optical film is measured according to the following steps (1) to (3). The following steps (1) to (3) can be measured, for example, by using the "DropMaster" series product number "DMo-701" of Kyowa Interface Science Co., Ltd. and using "SA-301" as an accessory.
[0114] As pure water, general-purpose pure water can be used. Generally, the resistivity value of pure water is 0.1 MΩ·cm or more and 15 MΩ·cm or less.
[0115] (1) Cut a sample of 2 cm × 8 cm from the optical film. Stick a double-sided tape on the second side of the sample, and fix the sample to a horizontal table with an inclination angle of 0 degrees via the double-sided tape. The size of the double-sided tape is more than 8 cm long and 5 mm wide. When fixing the sample to the table, make sure that no wrinkles are generated on the sample and that no air bubbles enter between the sample and the table.
[0116] (2) Add 30 μl of pure water to the first surface of the sample.
[0117] (3) The stage on which the sample is placed is gradually tilted at a speed of 2° / 1 second. When the tip of the droplet moves more than 0.2835 mm, the droplet is judged to be flowing down. The angle of the stage when the droplet flows down is referred to as the "pure water falling inclination angle". The "angle of the stage" refers to the angle formed by the horizontal plane and the plane of the stage.
[0118] Figure 3 This is a diagram for explaining the inclination angle (degrees) of pure water droplets when they flow down. Figure 3 The "θ" of the table is equivalent to the angle of the table. Figure 3 In FIG. 1 , reference numeral 200 indicates a horizontal plane, reference numeral 300 indicates a plane of a stage, and reference numeral 400 indicates a droplet. Figure 3 In the figure, the optical film between the flat surface 300 of the stage and the liquid-liquid 400 is omitted.
[0119] In this specification, Vmp, Vvc, and Vvv are calculated by setting the load area ratio separating the core portion from the protruding peak portion to 10% and the load area ratio separating the core portion from the protruding valley portion to 80%.
[0120] In this specification, Sxp mentioned later means the difference between the height at which the load area ratio is 2.5% and the height at which the load area ratio is 50%.
[0121] Unless otherwise specified, the description "In this specification, xxx." refers to the description common to the first embodiment and the second embodiment. For example, the definition of Vmp and the like described above is the description common to the first embodiment and the second embodiment.
[0122] In this specification, surface shapes such as Sa, Vmp, Vvv, Vvc, Sxp, and Sal are measured using a confocal laser microscope. Examples of confocal laser microscopes include the "VK-X" series from KEYENCE. In addition, by using the "Multi-file Analysis Application" of the "VK-X" series, Sa, Vmp, Vvv, Vvc, Sxp, and Sal can be easily calculated.
[0123] Regarding the measurement conditions when using the above-mentioned "VK-X" series to measure Sa, Vmp, Vvv, Vvc, Sxp and Sal, it is preferred to follow the conditions described in the embodiments. For example, the F-operation is preferably set to plane tilt correction (region designation). Regarding the measurement area, it is preferably a rectangle with a side of 50 μm or more and 200 μm or less, and regarding the measurement points, it is preferably 500 points or more and 2000 points or less on each side.
[0124] In this specification, the surface shape (Sa, Vmp, Vvv, Vvc, Sxp and Sal), angle (pure water drop inclination angle, pure water contact angle and drop contact angle), element ratio (F / inorganic Si, organic Si / inorganic Si, F / organic Si, etc.), optical properties (R SCI , haze, total light transmittance, transmitted image clarity, etc.), unless otherwise specified, refers to the average value of the measured values at 14 locations after excluding the maximum and minimum values from the measured values at 16 locations.
[0125] In this specification, regarding the 16 measurement positions, the area 1 cm from the outer edge of the measurement sample is removed as a blank, and for the remaining area, the 16 positions of the intersection when the lines dividing the longitudinal and transverse directions into 5 equal parts are drawn are used as the center of the measurement. For example, in the case where the measurement sample is a rectangle, the area 0.5 cm from the outer edge of the rectangle is removed as a blank, and the 16 positions of the intersection of the dotted lines dividing the remaining area into 5 equal parts in the longitudinal and transverse directions are used as the center for measurement. Then, the average value of the 14 measurement values after removing the maximum and minimum values from the measurement values at the 16 positions is used as the value of the parameter. In the case where the measurement sample is a shape other than a rectangle, such as a circle, an ellipse, a triangle, a pentagon, etc., a rectangle inscribed in these shapes is drawn, and about the rectangle, 16 measurements are performed by the above method.
[0126] In this specification, the surface shape (Sa, Vmp, Vvv, Vvc, Sxp and Sal), angle (pure water drop inclination angle, pure water contact angle and drop contact angle), surface tension, element ratio (F / inorganic Si, organic Si / inorganic Si, F / organic Si, etc.), optical properties (R SCI , haze, total light transmittance, transmitted image clarity, etc.), unless otherwise specified, are values measured at a temperature of 23±5°C and a relative humidity of 40% to 65%. In addition, before each measurement, the target sample is exposed to the above atmosphere for 30 minutes to 60 minutes, and then the measurement is performed.
[0127] In the optical film of the first embodiment of the present disclosure, the protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2Above and 0.100ml / m 2 Vvv is a parameter indicating the volume of the protruding portion deeper than the core. By setting Vvv to 0.005 ml / m 2 By setting Vvv to 0.100 ml / m 2 The fingerprint wiping property can be easily improved as follows.
[0128] The lower limit of Vvv is more preferably 0.007 ml / m 2 More preferably, 0.010 ml / m 2 The upper limit of Vvv is more preferably 0.080 ml / m 2 Below, more preferably 0.060 ml / m 2 the following.
[0129] Regarding the embodiment of the range of Vvv of the first surface, 0.005 ml / m 2 Above and 0.100ml / m 2 Below, 0.005ml / m 2 Above and 0.080ml / m 2 Below, 0.005ml / m 2 Above and 0.060ml / m 2 Below, 0.007ml / m 2 Above and 0.100ml / m 2 Below, 0.007ml / m 2 Above and 0.080ml / m 2 Below, 0.007ml / m 2 Above and 0.060ml / m 2 Below, 0.010ml / m 2 Above and 0.100ml / m 2 Below, 0.010ml / m 2 Above and 0.080ml / m 2 the following.
[0130] In the first embodiment, for the first surface of the optical film of the present disclosure, the ratio of Vvv to the core space volume Vvc specified by ISO 25178-2:2012 (Vvv / Vvc) is preferably 0.10 or less. By setting Vvv / Vvc to 0.10 or less, fingerprint wiping properties can be easily improved. Vvv / Vvc is more preferably 0.09 or less, and further preferably 0.08 or less.
[0131] In the first embodiment, for the first surface of the optical film of the present disclosure, the ratio of Vmp to Vvc (Vmp / Vvc) is preferably 0.10 or less. By making Vmp / Vvc 0.10 or less, it is easy to make the fingerprint wiping property better. Vvv / Vvc is more preferably 0.09 or less, and further preferably 0.08 or less.
[0132] In the first embodiment, regarding the first surface of the optical film of the present disclosure, the minimum autocorrelation length Sal specified by ISO 25178-2:2012 is preferably 4.0 μm or more and 12.0 μm or less.
[0133] Sal is a parameter that focuses on the lateral direction. The smaller Sal is, the more densely concave and convex the first surface is, and the larger Sal is, the wider the intervals between concave and convex the first surface is. For the value of "average length RSm of roughness curve elements" specified by JIS B0601, fine concave and convex have almost no effect, and only large concave and convex have an effect. On the other hand, for the value of Sal, not only large concave and convex have an effect, but also fine concave and convex have an effect, which is different from RSm. In addition, even if the intervals between concave and convex are wider, if the convex portion is small or the concave and convex shape is complex, Sal tends to become smaller. In addition, if the convex portion is a monotonous shape, there is a tendency for Sal to become larger.
[0134] The description in this paragraph is common to the first embodiment and the second embodiment.
[0135] By setting Sal to 4.0 μm or more, fingerprint wiping properties can be easily improved, and by setting Sal to 12.0 μm or less, anti-glare properties can be easily improved.
[0136] The lower limit of Sal is more preferably 5.0 μm or more, and further preferably 6.0 μm or more. The upper limit of Sal is more preferably 11.0 μm or less, and further preferably 10.0 μm or less.
[0137] Regarding the implementation methods of the range of Sal of the first surface, there can be listed as 4.0μm or more and 12.0μm or less, 4.0μm or more and 11.0μm or less, 4.0μm or more and 10.0μm or less, 5.0μm or more and 12.0μm or less, 5.0μm or more and 11.0μm or less, 5.0μm or more and 10.0μm or less, 6.0μm or more and 12.0μm or less, 6.0μm or more and 11.0μm or less, and 6.0μm or more and 10.0μm or less.
[0138] The description in this paragraph is common to the first embodiment and the second embodiment.
[0139] In the first embodiment, regarding the optical film of the present disclosure, it is preferred that the element ratios obtained by analyzing the surface region of the first surface side by X-ray photoelectron spectroscopy satisfy the following formulas 2 to 4.
[0140] 3.5≤F / inorganic Si≤10.0 (Formula 2),
[0141] 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3),
[0142] 5.0≤F / organic Si≤50.0 (Formula 4),
[0143] In Formulae 2 to 4, "F" is the ratio of fluorine element, "inorganic Si" is the ratio of silicon element belonging to the inorganic silicon compound, and "organic Si" is the ratio of silicon element belonging to the organic silicon compound.
[0144] In this specification, "surface region on the first surface side" means a region from the surface of the first surface side to a depth of 10 nm. In this specification, "X-ray photoelectron spectroscopy" is sometimes referred to as "XPS". In this specification, the element ratio of the surface region on the first surface side can be measured by the method described in the examples.
[0145] The inorganic Si in the surface region of the first surface of the optical film is mainly derived from the silica particles. The organic Si and F in the surface region of the first surface of the optical film are mainly derived from the leveling agent.
[0146] Inorganic Si and organic Si can be separated by performing peak separation of inorganic components and organic components in the X-ray photoelectron spectrum of Si 2p orbital.
[0147] The description in this paragraph is common to the first embodiment and the second embodiment.
[0148] In the surface region of the first surface of the optical film, inorganic Si can reduce the refractive index of the first surface, but on the other hand, there is a tendency to deteriorate the fingerprint wiping property. In addition, by including a predetermined amount of organic Si and F relative to inorganic Si in the surface region of the first surface of the optical film, there is a tendency to improve the fingerprint wiping property. Furthermore, by including organic Si and F in a well-balanced manner in the surface region of the first surface of the optical film, there is a tendency to improve the fingerprint wiping property. Therefore, by setting F / inorganic Si to 3.5 or more, organic Si / inorganic Si to 0.08 or more, and F / organic Si to 5.0 or more and 50.0 or less, Sw can be easily reduced, thereby easily satisfying Formula 1.
[0149] Furthermore, by setting F / inorganic Si to 10.0 or less and organic Si / inorganic Si to 1.00 or less, it is possible to easily suppress a decrease in the coating properties of the antireflection layer.
[0150] Regarding F / inorganic Si, the lower limit is more preferably 4.0 or more, and further preferably 4.5 or more, and the upper limit is more preferably 9.0 or less, and further preferably 8.0 or less.
[0151] Regarding organic Si / inorganic Si, the lower limit is more preferably 0.10 or more, and further preferably 0.15 or more, and the upper limit is more preferably 0.80 or less, and further preferably 0.50 or less.
[0152] Regarding F / organic Si, the lower limit is more preferably 10.0 or more, further preferably 15.0 or more, and further preferably 22.0 or more, and the upper limit is more preferably 40.0 or less, and further preferably 35.0 or less.
[0153] The description in this paragraph is common to the first embodiment and the second embodiment.
[0154] Regarding the implementation of the range of F / inorganic Si, examples include 3.5 or more and 10.0 or less, 3.5 or more and 9.0 or less, 3.5 or more and 8.0 or less, 4.0 or more and 10.0 or less, 4.0 or more and 9.0 or less, 4.0 or more and 8.0 or less, 4.5 or more and 10.0 or less, 4.5 or more and 9.0 or less, and 4.5 or more and 8.0 or less.
[0155] Regarding the embodiments of the range of organic Si / inorganic Si, there are listed 0.08 to 1.00, 0.08 to 0.80, 0.08 to 0.50, 0.10 to 1.00, 0.10 to 0.80, 0.10 to 0.50, 0.15 to 1.00, 0.15 to 0.80, and 0.15 to 0.50.
[0156] Regarding the embodiment of the range of F / organic Si, examples include 5.0 to 50.0, 5.0 to 40.0, 5.0 to 35.0, 10.0 to 50.0, 10.0 to 40.0, 10.0 to 35.0, 15.0 to 50.0, 15.0 to 40.0, 15.0 to 35.0, 22.0 to 50.0, 22.0 to 40.0, and 22.0 to 35.0.
[0157] The description in this paragraph is common to the first embodiment and the second embodiment.
[0158] In the optical film disclosed herein, regarding the element ratio obtained by analyzing the surface area on the first surface side by X-ray photoelectron spectroscopy, the ratio of inorganic Si to all elements is preferably 2 atomic % or more and 20 atomic % or less. By making the ratio of inorganic Si to all elements 2 atomic % or more, the refractive index of the first surface can be easily reduced, so that the anti-reflective property of the optical film can be easily improved. By making the ratio of inorganic Si 20 atomic % or less, F / inorganic Si can be easily made 3.5 or more, and organic Si / inorganic Si can be made 0.08 or more.
[0159] The lower limit of the ratio of inorganic Si to all elements is more preferably 3 atomic % or more, and further preferably 4 atomic % or more, and the upper limit is more preferably 15 atomic % or less, and further preferably 12 atomic % or less.
[0160] Regarding the implementation methods of the ratio range of inorganic Si to all elements, there can be listed more than 2 atomic % and less than 20 atomic %, more than 2 atomic % and less than 15 atomic %, more than 2 atomic % and less than 12 atomic %, more than 3 atomic % and less than 20 atomic %, more than 3 atomic % and less than 15 atomic %, more than 3 atomic % and less than 12 atomic %, more than 4 atomic % and less than 20 atomic %, more than 4 atomic % and less than 15 atomic %, and more than 4 atomic % and less than 12 atomic %.
[0161] The description in this paragraph is common to the first embodiment and the second embodiment.
[0162] <Layered Structure>
[0163] The optical film of the first embodiment of the present disclosure includes an antireflection layer and an antiglare layer in this order from the first surface toward the second surface. The outermost surface of the first surface side of the optical film of the first embodiment is preferably an antireflection layer.
[0164] The optical film of the present disclosure may have layers other than the antireflection layer and the antiglare layer. Examples of the layers other than the antireflection layer and the antiglare layer include a substrate, an antistatic layer, and an adhesive layer.
[0165] The optical film of the present disclosure preferably includes an antireflection layer, an antiglare layer, and a substrate in this order from the first surface toward the second surface.
[0166] The description in this paragraph is common to the first embodiment and the second embodiment.
[0167] Substrate
[0168] For ease of production and ease of handling, the optical film of the first embodiment preferably has a substrate.
[0169] As a substrate, it is preferred that it has light transmittance, smoothness and heat resistance, and has excellent mechanical strength. As such a substrate, there can be listed plastic films such as polyester, triacetyl cellulose (TAC), cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyether sulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, polymethyl methacrylate, polycarbonate, polyurethane and amorphous olefin (Cyclo-Olefin-Polymer: COP). The substrate can also be formed by laminating two or more plastic films.
[0170] Among plastic films, polyester films processed by stretching are preferred for mechanical strength and dimensional stability, and polyester films processed by biaxial stretching are more preferred. Polyethylene terephthalate films, polyethylene naphthalate films, etc. can be cited as polyester films. TAC films and acrylic films are preferred because they can easily improve light transmittance and optical isotropy. COP films and polyester films are preferred because they have excellent weather resistance.
[0171] The description in this paragraph is common to the first embodiment and the second embodiment.
[0172] The thickness of the substrate is preferably 5 μm or more and 300 μm or less, more preferably 20 μm or more and 200 μm or less, and further preferably 30 μm or more and 120 μm or less.
[0173] When the optical film is to be thinned, the upper limit of the thickness of the substrate is preferably 100 μm or less, and the more preferred upper limit is 80 μm or less. In addition, when the substrate is a low moisture permeability substrate such as polyester, COP, acrylic acid, the upper limit of the thickness of the substrate used for thinning is preferably 60 μm or less, and the more preferred upper limit is 40 μm or less. Even in the case of a large screen, if the upper limit of the thickness of the substrate is within the above range, it is also preferred in that deformation is difficult to occur.
[0174] In this specification, the thickness of the substrate is measured by a film thickness measuring instrument. Examples of film thickness measuring instruments include Mitutoyo's digital display standard external micrometer (model: MDC-25SX). For the thickness of the substrate, the average value obtained by measuring any 10 points is sufficient as the above value.
[0175] The description in this paragraph is common to the first embodiment and the second embodiment.
[0176] Regarding the substrate, the total light transmittance of JIS K7361-1:1997 is preferably 70% or more, more preferably 80% or more, and even more preferably 85% or more.
[0177] The substrate has a haze of preferably 10% or less, more preferably 5% or less, and further preferably 3% or less in accordance with JIS K7136:2000.
[0178] In order to improve the adhesiveness, the surface of the substrate may be subjected to a physical treatment such as a corona discharge treatment, or a chemical treatment. In addition, the substrate may have an easy-adhesion layer on the surface.
[0179] The description in this paragraph is common to the first embodiment and the second embodiment.
[0180] Anti-glare layer
[0181] In the first embodiment, the antiglare layer is a layer that plays a central role in antiglare properties.
[0182] In the first embodiment, the anti-glare layer can be formed by, for example, (A) a method using an embossing roller, (B) etching treatment, (C) molding based on a mold, (D) coating film formation based on coating, etc. In order to easily obtain a stable surface shape, molding based on a mold in (C) is preferred, and in order to improve productivity and cope with multiple varieties, coating film formation based on coating in (D) is preferred.
[0183] In the method of (C), for example, by allowing the resin to flow into a mold and taking the molded resin out of the mold, an anti-glare layer can be formed. The molded resin taken out of the mold can be arranged on a substrate. For the mold, a mold that reverses the surface shape of the anti-glare layer is used. Such a mold can be made, for example, by the following methods (c1-1) to (c1-2) or the following method (c2).
[0184] (c1-1) A shape in which Sa, Vmp, etc. fall within a predetermined range is created by simulation. Furthermore, the simulated shape is inverted.
[0185] (c1-2) The surface of the metal is engraved with a laser or processed with photolithography so that the inverted shape is reflected, thereby obtaining a mold.
[0186] (c2) A mold having a shape reversed from that of the anti-glare layer produced in (D) is obtained by a general electroforming method.
[0187] When the anti-glare layer is formed by (D), for example, the following methods (d1) and (d2) are mentioned. (d1) is preferred because the range of the surface shape such as Sa and Vmp can be adjusted more easily than (d2).
[0188] (d1) A method of applying and drying a coating liquid containing a binder resin and particles to form an anti-glare layer having unevenness due to the particles.
[0189] (d2) A method of forming projections and depressions by applying a coating liquid containing an arbitrary resin and a resin having poor compatibility with the above-mentioned resin, and causing the resin to phase separate.
[0190] -thickness-
[0191] In order to achieve a balance between curl suppression, mechanical strength, hardness, and toughness, the thickness T of the antiglare layer is preferably 2.0 μm to 10.0 μm, more preferably 3.0 μm to 8.0 μm, and further preferably 4.0 μm to 6.0 μm.
[0192] In this specification, the thickness of the anti-glare layer can be calculated by, for example, selecting any 20 locations on a cross-sectional photograph of an optical film obtained using a scanning transmission electron microscope and calculating the average value thereof. Preferably, the accelerating voltage of the STEM is 10 kV or more and 30 kV or less, and the magnification of the STEM is 1000 times or more and 7000 times or less.
[0193] The description in this paragraph is common to the first embodiment and the second embodiment.
[0194] -Element-
[0195] The anti-glare layer preferably mainly comprises a resin component. Furthermore, the anti-glare layer may also comprise, as required: particles such as organic particles and inorganic particles; nanometer-sized microparticles; and other components such as additives such as a refractive index adjuster, an antistatic agent, a leveling agent, an ultraviolet absorber, a light stabilizer, an antioxidant, a viscosity adjuster, and a thermal polymerization initiator.
[0196] The description in this paragraph is common to the first embodiment and the second embodiment.
[0197] The antiglare layer preferably contains a binder resin and particles.
[0198] Regarding particles, organic particles and inorganic particles can be listed, and inorganic particles are preferred. That is, the anti-glare layer preferably contains a binder resin and inorganic particles. In addition, the anti-glare layer more preferably contains a binder resin, inorganic particles and organic particles.
[0199] The description in this paragraph is common to the first embodiment and the second embodiment.
[0200] - Particles -
[0201] Examples of the inorganic particles include silica, alumina, zirconia, and titania, and silica is preferred. Among the inorganic particles, amorphous inorganic particles are preferred, and amorphous silica is more preferred.
[0202] Examples of the organic particles include particles containing one or more resins selected from polymethyl methacrylate, polyacrylic acid-styrene copolymers, melamine resins, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensates, silicones, fluorine-based resins, polyester-based resins, and the like.
[0203] Amorphous inorganic particles are inorganic particles having no specific shape and are obtained by pulverizing inorganic particles having a large particle size and then classifying them.
[0204] The particles preferably include inorganic particles. In addition, the particles more preferably include amorphous inorganic particles, and further preferably include amorphous inorganic particles and organic particles. The amorphous inorganic particles are preferably amorphous silica.
[0205] The description in this paragraph is common to the first embodiment and the second embodiment.
[0206] Compared with spherical particles, amorphous inorganic particles have a tendency to easily increase Sa and easily reduce Sal. However, if the particle size distribution of the amorphous inorganic particles is too wide, Vmp tends to become larger, so it is difficult to satisfy Formula 1. In particular, if the amorphous inorganic particles agglomerate, Vmp becomes larger, making it more difficult to satisfy Formula 1. On the other hand, if the particle size distribution of the amorphous inorganic particles is too narrow, the coating adaptability is easily reduced. Therefore, the volume-based cumulative distribution of the particle size of the amorphous inorganic particles is preferably in the range described later. However, if inorganic particles are used alone, agglomeration is likely to occur. Therefore, in the first embodiment, in order to easily satisfy Sa and Formula 1, it is preferred to set the particle size distribution of the amorphous particles to the range described later and use organic particles in combination.
[0207] In the first embodiment, regarding inorganic particles such as amorphous inorganic particles, it is preferred that the volume-based cumulative distribution d10 of particle size, the volume-based cumulative distribution d50 of particle size, and the volume-based cumulative distribution d90 of particle size satisfy the following relationships (1) and (2).
[0208] 1.5≤d50 / d10≤4.0 (1)
[0209] 1.0≤d90 / d50≤3.0 (2)
[0210] D50 / d10 being 1.5 or more means that the particle size distribution of the inorganic particles in the region below the average is wider. By setting d50 / d10 to more than 1.5, it is easy to give fine concavoconvex to the concavoconvex surface, so Sal can be easily reduced. By setting d50 / d10 to less than 4.0, it is possible to suppress the amount of inorganic particles buried in the anti-glare layer to increase, thereby improving the addition efficiency of inorganic particles.
[0211] d90 / d50 being 1.0 or more means that the particle size distribution of the inorganic particles in the region where the particle size is above the average is wide. By setting d90 / d50 to 1.0 or more, Vmp can be easily increased and Sal can be easily increased. By setting d90 / d50 to 3.0 or less, Vmp can be easily suppressed from becoming too large and Sal from becoming too large.
[0212] The lower limit of d50 / d10 is more preferably 2.0 or more, and further preferably 2.3 or more, and the upper limit is more preferably 3.5 or less, and further preferably 3.2 or less.
[0213] The lower limit of d90 / d50 is more preferably 1.3 or more, and still more preferably 1.5 or more, and the upper limit is more preferably 2.5 or less, and still more preferably 2.0 or less.
[0214] In this specification, d10, d50, and d90 of inorganic particles such as amorphous inorganic particles are measured by a laser diffraction method.
[0215] In the first embodiment, the volume-based cumulative distribution d50 of the particle size of inorganic particles such as amorphous inorganic particles is preferably 2.5 μm to 5.5 μm, more preferably 3.0 μm to 5.0 μm, and further preferably 3.3 μm to 4.7 μm.
[0216] By setting d50 to 2.5 μm or more, the number of inorganic particles can be prevented from excessively increasing, so that Sal can be easily prevented from becoming too small. By setting d50 to 5.5 μm or less, the number of inorganic particles can be prevented from excessively decreasing, so that Sal can be easily prevented from becoming too large.
[0217] Regarding the thickness T of the antiglare layer and d50 of inorganic particles such as amorphous inorganic particles, d50 / T is preferably 0.55 to 1.00, more preferably 0.60 to 0.95, and further preferably 0.70 to 0.90.
[0218] By setting d50 / T to be 0.55 or more, Sal can be easily reduced, and by setting d50 / T to be 1.00 or less, Sal can be easily increased.
[0219] The description in this paragraph is common to the first embodiment and the second embodiment.
[0220] Regarding the thickness T of the antiglare layer and d90 of inorganic particles such as amorphous inorganic particles, d90 / T is preferably 1.00 to 1.50, more preferably 1.08 to 1.45, and further preferably 1.20 to 1.40.
[0221] By setting d90 / T to be 1.00 or more, Vmp can be easily increased, and by setting d90 / T to be 1.50 or less, Vmp can be easily decreased.
[0222] The description in this paragraph is common to the first embodiment and the second embodiment.
[0223] The content of the inorganic particles such as amorphous inorganic particles is preferably 8 parts by mass to 40 parts by mass, more preferably 12 parts by mass to 30 parts by mass, and further preferably 15 parts by mass to 28 parts by mass, relative to 100 parts by mass of the binder resin.
[0224] By making the content of inorganic particles such as amorphous inorganic particles 8 parts by mass or more, it is possible to suppress the excessive reduction in the number of inorganic particles, so that the inorganic particles are densely arranged, thereby forming valleys between the inorganic particles. Therefore, Vvv becomes above a specified value, and then Sal does not become too large, so it is easy to make the anti-glare property good.
[0225] By setting the content of inorganic particles such as amorphous inorganic particles to 40 parts by mass or less, it is possible to suppress an excessive increase in the number of inorganic particles, and thus it is possible to easily suppress Sal from becoming too small.
[0226] The description in this paragraph is common to the first embodiment and the second embodiment.
[0227] In the first embodiment, the content of the organic particles is preferably 1 to 25 parts by mass, more preferably 3 to 18 parts by mass, and further preferably 8 to 14 parts by mass, relative to 100 parts by mass of the binder resin.
[0228] By making the content of organic particles 1 part by mass or more, the aggregation of inorganic particles can be easily suppressed. In addition, by making the content of organic particles 1 part by mass or more, the number of organic particles can be suppressed from being excessively reduced, so that Vmp can be easily suppressed from becoming too large.
[0229] Since the particle size distribution of organic particles is relatively uniform, if the content of organic particles increases, the tendency of Sal to become smaller increases. Therefore, by making the content of organic particles less than 25 parts by mass, it is possible to prevent Sal from becoming too small and easily make fingerprint wiping properties good.
[0230] In the first embodiment, the average particle diameter of the organic particles is preferably 1.0 μm or more and 5.0 μm or less, more preferably 1.2 μm or more and 3.0 μm or less, and further preferably 1.3 μm or more and 2.5 μm or less.
[0231] By making the average particle size of the organic particles greater than 1.0 μm, the number of organic particles can be suppressed from excessively increasing, so it is easy to suppress Sal from becoming too small. Therefore, by making the average particle size of the organic particles greater than 1.0 μm, it is easy to make the fingerprint wiping property good. By making the average particle size of the organic particles less than 5.0 μm, the number of organic particles can be suppressed from excessively decreasing, so it is easy to suppress Vmp from becoming too large.
[0232] In this specification, the average particle size of organic particles refers to a value determined as a volume average value d50 in a laser diffraction method.
[0233] In the first embodiment, the particle size distribution of the organic particles is preferably narrow. Specifically, in the first embodiment, the proportion of particles within the range of ±0.5 μm of the average particle size of the organic particles is preferably 80% by volume or more of the total amount of the organic particles, more preferably 85% by volume or more, and further preferably 90% or more. By making the particle size distribution of inorganic particles such as amorphous inorganic particles wider and narrowing the particle size distribution of organic particles, Vmp can be reduced and Formula 1 can be easily satisfied.
[0234] Examples of the shape of the organic particles include spherical, disc-shaped, rugby-ball-shaped, and irregular shapes. Among these shapes, spherical organic particles are preferred because they can easily control the particle size distribution.
[0235] The description in this paragraph is common to the first embodiment and the second embodiment.
[0236] In the first embodiment, the ratio of the average particle size of the organic particles to the thickness of the anti-glare layer (average particle size of the organic particles / thickness of the anti-glare layer) is preferably 0.20 or more and 0.70 or less, more preferably 0.23 or more and 0.50 or less, and further preferably 0.25 or more and 0.35 or less. By making the average particle size of the organic particles / thickness of the anti-glare layer be the above range, Vmp, Sa and Sal can be easily made to be the above range.
[0237] -Inorganic particles-
[0238] The anti-glare layer may further contain inorganic fine particles in addition to the binder resin and the particles. In the present specification, the inorganic fine particles can be distinguished from the above-mentioned particles by the average particle size.
[0239] When the anti-glare layer contains inorganic fine particles, the difference between the refractive index of the particles and the refractive index of the composition of the anti-glare layer other than the particles becomes small, and the internal haze can be easily reduced.
[0240] The description in this paragraph is common to the first embodiment and the second embodiment.
[0241] Examples of the inorganic fine particles include fine particles made of silica, alumina, zirconia, titania, etc. Among them, silica is preferred because it is easy to suppress the generation of internal haze.
[0242] The average particle diameter of the inorganic fine particles is preferably 1 nm or more and 200 nm or less, more preferably 2 nm or more and 100 nm or less, and further preferably 5 nm or more and 50 nm or less.
[0243] The description in this paragraph is common to the first embodiment and the second embodiment.
[0244] -Binder resin-
[0245] In order to easily improve the scratch resistance, the binder resin preferably contains a cured product of a curable resin composition such as a cured product of a thermosetting resin composition or a cured product of an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.
[0246] The binder resin may contain a thermoplastic resin within a range not impairing the effects of the present disclosure.
[0247] In order to easily improve the scratch resistance, the ratio of the cured product of the curable resin composition to the total amount of the binder resin is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 100% by mass.
[0248] The thermosetting resin composition is a composition containing at least a thermosetting resin, and is a resin composition that is cured by heating.
[0249] Examples of the thermosetting resin include acrylic resin, polyurethane resin, phenolic resin, urea-melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.
[0250] The description in this paragraph is common to the first embodiment and the second embodiment.
[0251] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter also referred to as an “ionizing radiation curable compound”).
[0252] As the ionizing radiation curable functional group, ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, and allyl, as well as epoxy, oxetanyl, etc. can be listed. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and a compound having two or more ethylenically unsaturated bond groups is more preferred, wherein a polyfunctional (meth) acrylate compound having two or more ethylenically unsaturated bond groups is further preferred. As the polyfunctional (meth) acrylate compound, any one of a monomer and an oligomer can be used.
[0253] In this specification, ionizing radiation refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules. Regarding ionizing radiation, ultraviolet rays (UV) or electron beams (EB) are generally used, and in addition, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays may also be used.
[0254] The description in this paragraph is common to the first embodiment and the second embodiment.
[0255] Examples of the bifunctional (meth)acrylate monomer in the polyfunctional (meth)acrylate compound include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, and 1,6-hexanediol diacrylate.
[0256] Examples of the trifunctional or higher-functional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.
[0257] The (meth)acrylate monomers may be monomers in which a part of the molecular skeleton is modified. For example, monomers in which a part of the molecular skeleton is modified by ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. may be used.
[0258] The description in this paragraph is common to the first embodiment and the second embodiment.
[0259] Examples of the polyfunctional (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.
[0260] Urethane (meth)acrylate can be obtained by, for example, a reaction between a polyol and an organic diisocyanate and a hydroxy (meth)acrylate.
[0261] Preferred epoxy (meth)acrylates are: (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with (meth)acrylic acid; (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with polybasic acids and (meth)acrylic acid; and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with phenols and (meth)acrylic acid.
[0262] The weight average molecular weight of the polyfunctional (meth)acrylate oligomer is preferably 500 to 3,000, and more preferably 700 to 2,500.
[0263] In this specification, the weight average molecular weight is measured by GPC analysis, and is an average molecular weight converted into standard polystyrene.
[0264] The description in this paragraph is common to the first embodiment and the second embodiment.
[0265] For the purpose of adjusting the viscosity of the anti-glare layer coating solution, a monofunctional (meth)acrylate may be used as an ionizing radiation curable compound. Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate.
[0266] The above-mentioned ionizing radiation-curable compounds may be used alone or in combination of two or more.
[0267] The description in this paragraph is common to the first embodiment and the second embodiment.
[0268] When the ionizing radiation curable compound is an ultraviolet curable compound, the ionizing radiation curable composition preferably contains an additive such as a photopolymerization initiator or a photopolymerization accelerator.
[0269] Examples of the photopolymerization initiator include one or more selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoylbenzoate, α-acyl oxime ester, thioxanthones and the like.
[0270] The photopolymerization accelerator can reduce polymerization hindrance caused by air during curing and accelerate the curing speed. Examples of the accelerator include isopentyl p-dimethylaminobenzoate and ethyl p-dimethylaminobenzoate.
[0271] The description in this paragraph is common to the first embodiment and the second embodiment.
[0272] In the first embodiment, when the binder resin includes a cured product of an ionizing radiation curable resin composition, the ionizing radiation curable resin composition preferably includes a polyfunctional (meth)acrylate monomer and a polyfunctional (meth)acrylate oligomer.
[0273] In the first embodiment, the mass ratio of the polyfunctional (meth)acrylate monomer to the polyfunctional (meth)acrylate oligomer is preferably 5:95 to 60:40, more preferably 20:80 to 60:40, and even more preferably 40:60 to 60:40.
[0274] By making the polyfunctional (meth)acrylate monomer into a predetermined ratio or more, the scratch resistance of the anti-glare layer can be easily improved.
[0275] By making the multifunctional (meth) acrylate oligomer more than the specified ratio, the viscosity of the anti-glare layer coating solution can be increased, particles can be easily suppressed from sinking to the bottom of the anti-glare layer, and the binder resin can be easily suppressed from flowing down between the convex portions based on the particles. Therefore, it is easy to make Sa and Vvv more than the specified values, and it is easy to make Sal less than the specified value. On the other hand, if the ratio of the multifunctional (meth) acrylate oligomer is too much, the strength of the anti-glare layer will sometimes decrease. In addition, if the viscosity of the anti-glare layer coating solution is too high, Vmp will sometimes become too large or Sal will become too small. Therefore, the ionizing radiation curable resin composition preferably includes a specified amount of multifunctional (meth) acrylate oligomer and a specified amount of multifunctional (meth) acrylate monomer.
[0276] -Solvents and drying conditions-
[0277] The anti-glare layer coating solution preferably contains a solvent in order to adjust the viscosity or dissolve or disperse the components. The surface shape of the anti-glare layer after coating and drying varies depending on the type of solvent, so it is preferred to select the solvent in consideration of the saturated vapor pressure of the solvent, the permeability of the solvent to the substrate, etc.
[0278] Specifically, the solvent includes, for example, ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (isopropyl alcohol, butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), glycol ethers (propylene glycol monomethyl ether acetate, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc., and a mixture thereof may be used.
[0279] The description in this paragraph is common to the first embodiment and the second embodiment.
[0280] In the first embodiment, the solvent in the anti-glare layer coating solution preferably has a solvent with a fast evaporation rate as the main component. By accelerating the evaporation rate of the solvent, it is possible to suppress the particles from sinking into the lower part of the anti-glare layer, and then it is easy to suppress the binder resin from flowing down between the convex parts based on the particles. Therefore, it is easy to make Sa and Vvv more than the specified values, and it is easy to make Sal less than the specified value.
[0281] The main component refers to 50% by mass or more of the total amount of the solvent, preferably 70% by mass or more, more preferably 90% by mass or more, and further preferably 97% by mass or more.
[0282] In the present specification, a solvent with a high evaporation rate refers to a solvent having an evaporation rate of 100 or more when the evaporation rate of butyl acetate is 100. The evaporation rate of the solvent with a high evaporation rate is more preferably 120 or more and 300 or less, and further preferably 150 or more and 220 or less.
[0283] Examples of solvents having a fast evaporation rate include methyl isobutyl ketone (evaporation rate: 160), toluene (evaporation rate: 200), and methyl ethyl ketone (evaporation rate: 370).
[0284] On the other hand, examples of the slow evaporation rate solvent having an evaporation rate of less than 100 include cyclohexanone (evaporation rate: 32) and propylene glycol monomethyl ether acetate (evaporation rate: 44).
[0285] The description in this paragraph is common to the first embodiment and the second embodiment.
[0286] In the first embodiment, when the anti-glare layer is formed from the anti-glare layer coating liquid, it is preferred to control the drying conditions.
[0287] The drying conditions can be controlled by the drying temperature and the wind speed in the dryer. The drying temperature is preferably 30° C. to 120° C., and the drying wind speed is preferably 0.2 m / s to 50 m / s. In addition, in order to control the surface shape of the anti-glare layer by drying, it is preferred to irradiate with ionizing radiation after the coating liquid is dried.
[0288] About drying conditions, preferably implement 2 stages of drying within the above-mentioned temperature range and wind speed range. And, preferably, compared with the drying in the first stage, in the drying in the second stage, make the drying temperature high temperature and make the wind speed stronger. By slowly drying in the first stage, thus, when the binder resin covers the surface of the amorphous inorganic particles, the shape of the amorphous inorganic particles can be easily reflected on the surface of the binder resin. In addition, by making the drying temperature in the second stage higher than the drying temperature in the first stage and strengthening the wind speed, the agglomeration of organic particles can be easily suppressed. Therefore, by adopting the drying in two stages, Vmp can be easily suppressed from becoming too large, and Sal can be easily made to be below the specified value.
[0289] In the first stage of drying, the drying temperature is preferably set to 30°C or more and less than 60°C, and the drying wind speed is preferably set to 0.2 m / s or more and less than 7 m / s. In the second stage of drying, the drying temperature is preferably set to 60°C or more and 120°C or less, and the drying wind speed is preferably set to 7 m / s or more and 50 m / s or less.
[0290] Anti-reflective layer
[0291] In the first embodiment, the antireflection layer is preferably located on the outermost surface on the first surface side.
[0292] For the anti-reflection layer, for example, a single-layer structure of a low refractive index layer; a two-layer structure of a high refractive index layer and a low refractive index layer; and a multilayer structure of more than three layers. The low refractive index layer and the high refractive index layer can be formed by a general wet method or a dry method. In the case of a wet method, the above-mentioned single-layer structure or two-layer structure is preferred, and in the case of a dry method, the above-mentioned multilayer structure is preferred.
[0293] The wet method is superior to the dry method in terms of production efficiency and chemical resistance.
[0294] In the optical film of the present disclosure, the antireflection layer is preferably a single-layer structure of a low-refractive index layer in order to easily maintain the uneven shape of the antiglare layer.
[0295] The description in this paragraph is common to the first embodiment and the second embodiment.
[0296] - Single-layer or two-layer structure -
[0297] The single-layer structure is a single layer of a low-refractive index layer, and the two-layer structure is formed of a high-refractive index layer and a low-refractive index layer. The single-layer structure or the two-layer structure is preferably formed by a wet method.
[0298] Examples of methods for forming an antireflection layer by a wet process include: a method of forming the layer by a sol-gel method using a metal alkoxide or the like; a method of forming the layer by coating a low-refractive-index resin such as a fluororesin; and a method of forming the layer by coating a coating liquid containing low-refractive-index particles or high-refractive-index particles in a binder resin composition.
[0299] In the wet method, in order to improve the close adhesion and scratch resistance, it is also preferred to form the anti-reflection layer using a coating solution containing low-refractive index particles or high-refractive index particles in the binder resin composition. That is, the low-refractive index layer preferably contains a binder resin and low-refractive index particles. In addition, the high-refractive index layer preferably contains a binder resin and high-refractive index particles.
[0300] The description in this paragraph is common to the first embodiment and the second embodiment.
[0301] The lower limit of the refractive index of the low refractive index layer is preferably 1.10 or more, more preferably 1.20 or more, more preferably 1.26 or more, more preferably 1.28 or more, more preferably 1.30 or more, and the upper limit is preferably 1.48 or less, more preferably 1.45 or less, more preferably 1.40 or less, more preferably 1.38 or less, more preferably 1.32 or less.
[0302] In this specification, the refractive index refers to a value at a wavelength of 550 nm.
[0303] The lower limit of the thickness of the low refractive index layer is preferably 80 nm or more, more preferably 85 nm or more, more preferably 90 nm or more, and the upper limit is preferably 150 nm or less, more preferably 110 nm or less, more preferably 105 nm or less.
[0304] The description in this paragraph is common to the first embodiment and the second embodiment.
[0305] In order to improve the scratch resistance, the binder resin of the low refractive index layer preferably contains a cured product of a curable resin composition such as a cured product of a thermosetting resin composition or a cured product of an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.
[0306] The binder resin of the low refractive index layer may contain a thermoplastic resin within a range not hindering the effects of the present disclosure.
[0307] Examples of the cured product of the curable resin composition of the low refractive index layer include the same cured products as those exemplified for the cured products of the curable resin composition in the anti-glare layer.
[0308] The ratio of the cured product of the curable resin composition to the total amount of the binder resin in the low refractive index layer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 97% by mass or more.
[0309] The description in this paragraph is common to the first embodiment and the second embodiment.
[0310] In the first embodiment, the binder resin of the low refractive index layer may also include a thermoplastic resin. By including a thermoplastic resin as the binder resin, the viscosity of the coating liquid for the low refractive index layer is increased, and the coating liquid for the low refractive index layer is not easy to flow down between the convex portions of the anti-glare layer. Therefore, by including a thermoplastic resin as the binder resin, it is easy to make Sa and Vvv above a specified value, and it is easy to make Sal below a specified value. Furthermore, since it is easy for organic Si and fluorine to remain near the surface of the first surface, it is easy to satisfy the element ratios of Formulas 2 to 4. On the other hand, if the viscosity of the coating liquid for the low refractive index layer becomes too high, defects may sometimes occur on the surface of the anti-glare layer when the coating liquid for the anti-reflection layer is applied.
[0311] Due to the above-mentioned effects and coating film strength, the content of the thermoplastic resin is preferably 0.1% by mass to 3.0% by mass, more preferably 0.2% by mass to 1.5% by mass, and further preferably 0.3% by mass to 0.7% by mass, based on the total amount of the binder resin.
[0312] Examples of the thermoplastic resin include polystyrene resins, polyolefin resins, ABS resins (including heat-resistant ABS resins), AS resins, AN resins, polyphenylene ether resins, polycarbonate resins, polyacetal resins, acrylic resins, polyethylene terephthalate resins, polybutylene terephthalate resins, polysulfone resins, and polyphenylene sulfide resins. From the viewpoint of transparency, acrylic resins are preferred.
[0313] The weight average molecular weight of the thermoplastic resin is preferably 20,000 to 200,000, more preferably 30,000 to 150,000, and even more preferably 50,000 to 100,000.
[0314] The description in this paragraph is common to the first embodiment and the second embodiment.
[0315] About low refractive index particles, hollow particles and solid particles can be listed. As low refractive index particles, only any one of hollow particles and solid particles can be included, but in order to reduce the refractive index, preferably hollow particles are included. In order to suppress the reduction of the coating strength of the low refractive index layer, in addition to hollow particles, solid particles can also be included. It should be noted that by not including solid particles and only including hollow particles, the effect of the present disclosure can be easily exerted.
[0316] The material of the hollow particles and the solid particles can be any inorganic compound such as silicon dioxide and magnesium fluoride, and any organic compound, but silicon dioxide is preferred for low refractive index and strength. That is, the low refractive index layer preferably includes hollow silica particles. In addition, it is also preferred that the low refractive index layer includes solid silica particles in addition to the hollow silica particles.
[0317] The description in this paragraph is common to the first embodiment and the second embodiment.
[0318] The average primary particle size of the hollow particles is preferably less than the thickness of the low refractive index layer, and for example, 1 nm or more and 150 nm or less can be cited. The average primary particle size of the hollow particles is preferably 35 nm or more and 100 nm or less, more preferably 50 nm or more and 100 nm or less, and further preferably 60 nm or more and 80 nm or less.
[0319] The average primary particle size of the solid particles is preferably smaller than the thickness of the low refractive index layer, and for example, 0.5 nm or more and 100 nm or less can be cited. The average primary particle size of the solid particles is preferably 1 nm or more and 30 nm or less, more preferably 5 nm or more and 20 nm or less, and further preferably 10 nm or more and 15 nm or less.
[0320] The description in this paragraph is common to the first embodiment and the second embodiment.
[0321] The average primary particle diameter of the hollow particles, the solid particles described below, and the high refractive particles described below is calculated by the following operations (A1) to (A3).
[0322] (A1) The cross section of the antireflection member is photographed using a TEM or STEM. Preferably, the acceleration voltage of the TEM or STEM is 10 kV to 30 kV, and the magnification is 50,000 to 300,000 times.
[0323] (A2) Ten random particles are extracted from the observed image, and the particle size of each particle is calculated. The particle size is measured as the distance between two random parallel straight lines that sandwich the cross section of the particle, and the distance between the two straight lines is the largest.
[0324] (A3) The same operation is performed five times on another observation image of the same sample, and the value obtained by the number average of the particle sizes of 50 particles in total is taken as the average primary particle size of the particles.
[0325] The description in this paragraph is common to the first embodiment and the second embodiment.
[0326] The more the content of hollow particles, the higher the filling rate of the hollow particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, the content of hollow particles is preferably 100 parts by mass or more, more preferably 150 parts by mass or more relative to 100 parts by mass of the binder resin.
[0327] On the other hand, if the content of hollow particles is too much, hollow particles are easily damaged or fall off, and there is a tendency that the mechanical strength such as the scratch resistance of the low-refractive index layer is reduced. In addition, if the content of hollow particles is too much, it is sometimes difficult to satisfy the above-mentioned formula 2 and formula 3. Therefore, the content of hollow particles is preferably less than 300 parts by mass, more preferably less than 250 parts by mass relative to 100 parts by mass of binder resin.
[0328] In order to improve the scratch resistance of the low refractive index layer, the content of the solid particles is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, based on 100 parts by mass of the binder resin.
[0329] On the other hand, if the content of solid particles is too much, the solid particles are easily agglomerated. In addition, if the content of solid particles is too much, it is sometimes difficult to satisfy the above-mentioned formula 2 and formula 3. Therefore, the content of solid particles is preferably 100 parts by mass or less, more preferably 60 parts by mass or less relative to 100 parts by mass of the binder resin.
[0330] The description in this paragraph is common to the first embodiment and the second embodiment.
[0331] In the first embodiment, in order to make it easier for the first surface to satisfy the element ratios of Formulae 2 to 4, the low refractive index layer preferably includes a leveling agent containing organic Si and fluorine.
[0332] The leveling agent containing organic Si and fluorine can be a compound containing organic Si and fluorine in the molecule. In addition, for the leveling agent containing organic Si and fluorine, a compound containing organic Si in the molecule and a compound containing fluorine in the molecule can be used together. In order to make the compatibility with the binder resin good, the low refractive index layer preferably contains a compound containing organic Si and fluorine in one molecule as a leveling agent. The leveling agent preferably has a functional group reactive with the binder resin in the molecule.
[0333] The element ratios of the above formulas 2 to 4 can be adjusted mainly by the content of the leveling agent and the ratio of organic Si and fluorine in the leveling agent. However, it is difficult to control the amount of the low refractive index layer coating liquid that flows down between the convex portions of the anti-glare layer by only relying on the content of the leveling agent and the ratio of organic Si and fluorine in the leveling agent. In order to easily satisfy the element ratios of the above formulas 2 to 4, it is preferred to increase the viscosity of the low refractive index layer coating liquid, or control the drying conditions of the low refractive index layer coating liquid, thereby reducing the amount of the low refractive index layer coating liquid that flows down between the convex portions of the anti-glare layer.
[0334] The description in this paragraph is common to the first embodiment and the second embodiment.
[0335] The preferred content of the leveling agent is preferably adjusted so as to satisfy the element ratios of Formulae 2 to 4 described above, depending on the ratio of organic Si to fluorine in the leveling agent.
[0336] In one embodiment of the present disclosure, the content of the leveling agent is preferably 10% by mass to 40% by mass, more preferably 15% by mass to 40% by mass, and further preferably 20% by mass to 40% by mass, relative to the total solid content of the low refractive index layer.
[0337] The description in this paragraph is common to the first embodiment and the second embodiment.
[0338] The high refractive index layer is preferably arranged closer to the anti-glare layer than the low refractive index layer.
[0339] The lower limit of the refractive index of the high refractive index layer is preferably 1.53 or more, more preferably 1.54 or more, more preferably 1.55 or more, more preferably 1.56 or more, and the upper limit is preferably 1.85 or less, more preferably 1.80 or less, more preferably 1.75 or less, more preferably 1.70 or less.
[0340] The upper limit of the thickness of the high refractive index layer is preferably 200 nm or less, more preferably 180 nm or less, further preferably 150 nm or less, and the lower limit is preferably 50 nm or more, more preferably 70 nm or more.
[0341] Examples of the binder resin for the high refractive index layer include the same binder resins as those for the low refractive index layer.
[0342] Examples of the high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide.
[0343] The average primary particle size of the high refractive index particles is preferably more than 2nm, more preferably more than 5nm, and further preferably more than 10nm. In addition, from the viewpoint of suppressing whitening and improving transparency, the average primary particle size of the high refractive index particles is preferably less than 200nm, more preferably less than 100nm, more preferably less than 80nm, more preferably less than 60nm, and more preferably less than 30nm.
[0344] The content of the high refractive index particles may be such that the refractive index of the high refractive index layer falls within the above-mentioned range.
[0345] The description in this paragraph is common to the first embodiment and the second embodiment.
[0346] When forming an anti-reflection layer such as a low refractive index layer and a high refractive index layer by a wet method, it is preferred to increase the viscosity of the anti-reflection layer coating liquid. By increasing the viscosity of the anti-reflection layer coating liquid, the anti-reflection layer coating liquid is not easy to flow down between the convex parts of the anti-glare layer. Therefore, even if the anti-reflection layer is formed on the anti-glare layer, the surface shape of the anti-glare layer can be easily maintained. Therefore, by appropriately increasing the viscosity of the anti-reflection layer coating liquid, Sa and Vvv can be easily made above the specified value, and Sal can be easily made below the specified value. Furthermore, since it is easy to make organic Si and fluorine remain near the surface of the first surface, it is easy to satisfy the element ratios of Formulas 2 to 4. For example, by adding a thermoplastic resin as a binder resin, or increasing the proportion of an oligomer as an ionizing radiation curable resin composition, or selecting a solvent with a high viscosity as a solvent, the viscosity of the anti-reflection layer coating liquid can be increased.
[0347] On the other hand, if the viscosity of the antireflection layer coating liquid is excessively increased, defects may be generated on the surface of the antiglare layer when the antireflection layer coating liquid is applied.
[0348] Therefore, the viscosity of the antireflection layer coating liquid at 23° C. is preferably 0.1 mPa·s or more and 5.0 mPa·s or less.
[0349] Examples of the solvent of the antireflection layer coating liquid include the same solvents as those in the embodiment of the antiglare layer coating liquid.
[0350] When forming the antiglare layer from the antireflection layer coating liquid, it is preferable to control the drying conditions.
[0351] The drying conditions can be controlled by the drying temperature and the wind speed in the dryer. The drying temperature is preferably above 30°C and below 70°C, and the drying wind speed is preferably above 10m / s and below 30m / s. By setting the drying temperature to a low temperature, the viscosity of the anti-reflection layer coating liquid can be easily increased. In addition, by increasing the wind speed, the viscosity of the anti-reflection layer coating liquid can be quickly increased. Therefore, by drying the anti-reflection layer coating liquid at a relatively low temperature and a relatively strong wind speed, the anti-reflection layer coating liquid can be prevented from flowing down between the convex portions of the anti-glare layer. That is, by drying the anti-reflection layer coating liquid at a relatively low temperature and a relatively strong wind speed, the surface shape such as Sa of the first surface can be easily made to be within the above-mentioned range, and Formulas 1 to 4 can be easily satisfied.
[0352] It is preferred that the irradiation with ionizing radiation is performed after the antireflection layer coating liquid is dried.
[0353] - In the case of a multi-layer structure with more than 3 layers -
[0354] The multilayer structure preferably formed by the dry method is a structure in which high refractive index layers and low refractive index layers are alternately stacked to form a total of three or more layers. In the multilayer structure, the low refractive index layer is preferably disposed on the outermost surface of the optical film.
[0355] The high refractive index layer preferably has a thickness of 10 nm to 200 nm, and a refractive index of 2.10 to 2.40. The high refractive index layer more preferably has a thickness of 20 nm to 70 nm.
[0356] The low refractive index layer preferably has a thickness of 5 nm to 200 nm, and a refractive index of 1.33 to 1.53. The thickness of the low refractive index layer is more preferably 20 nm to 120 nm.
[0357] The description in this paragraph is common to the first embodiment and the second embodiment.
[0358] <Optical Characteristics>
[0359] The optical film of the first embodiment preferably has a total light reflectance R measured by the following method: SCI Below 3.0%,
[0360] [Total light reflectance (R SCI )]
[0361] A sample was prepared in which a black plate was bonded to the second surface of the optical film via a transparent adhesive. The optical film side of the sample was used as the light incident surface to measure the total light reflectance (R SCI ).
[0362] By making RSCI The R of the optical film is 3.0% or less. Therefore, in an environment where light with strong illumination is not incident on the first surface, the black tone of the black display portion can be easily improved, and thus the contrast can be easily improved. SCI It is more preferably 2.5% or less, and even more preferably 2.0% or less. SCI The lower limit of is not particularly limited, but is usually 0.1% or more.
[0363] Usually, when R SCI When R is set to 3.0% or less, the contrast of the reflectance between the part with fingerprint components and the part without fingerprint components becomes large, and the aesthetics of the optical film is likely to be greatly reduced. However, in the optical film of the present disclosure, the fingerprint wiping property is good by satisfying Formula 1, so even if R is set to SCI When the content is 3.0% or less, it is also possible to easily suppress a decrease in the appearance of the optical film.
[0364] R SCI This is the reflected light measured by applying light to the sample surface from all directions using an integrating sphere and closing the light trap corresponding to the direction of regular reflection.
[0365] Representative R SCI The measuring device is a structure based on the geometric condition c of JIS Z8722:2009. More specifically, the representative R SCI The measurement device uses D65 as the light source of the integrating sphere spectrophotometer, the position of the light receptor is +8 degrees relative to the normal of the sample, the opening angle of the light receptor is 10 degrees, the position of the light trap is -8 degrees relative to the normal of the sample, and the viewing angle is 2 degrees or 10 degrees. In this specification, the viewing angle is set to 2 degrees.
[0366] As a measuring device satisfying the above conditions, for example, there is an integrating sphere spectrophotometer (trade name: CM-2002) manufactured by Konica Minolta Inc.
[0367] The description in this paragraph is common to the first embodiment and the second embodiment.
[0368] The difference between the refractive index of the transparent adhesive of the sample and the refractive index of the layer on the second surface side of the optical film is preferably within 0.05, more preferably within 0.03, and further preferably within 0.01. The difference between the refractive index of the transparent adhesive of the sample and the refractive index of the adhesive resin of the black plate is preferably within 0.05, more preferably within 0.03, and further preferably within 0.01.
[0369] The description in this paragraph is common to the first embodiment and the second embodiment.
[0370] The total light transmittance of the optical film in accordance with JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.
[0371] The light incident surface when measuring the total light transmittance and the haze is the second surface side of the optical film.
[0372] The description in this paragraph is common to the first embodiment and the second embodiment.
[0373] The haze of the optical film in JIS K7136:2000 is preferably 20% to 75%. The lower limit of the haze is more preferably 30% or more, further preferably 40% or more, further preferably 50% or more, and the upper limit is more preferably 70% or less, further preferably 65% or less.
[0374] By setting the haze to 20% or more, the anti-glare property can be easily improved, and by setting the haze to 75% or less, the reduction in the resolution of the image can be easily suppressed.
[0375] Regarding the implementation methods of the haze of the optical film, there can be listed more than 20% and less than 75%, more than 20% and less than 70%, more than 20% and less than 65%, more than 30% and less than 75%, more than 30% and less than 70%, more than 30% and less than 65%, more than 40% and less than 75%, more than 40% and less than 70%, more than 40% and less than 65%, more than 50% and less than 75%, more than 50% and less than 70%, and more than 50% and less than 65%.
[0376] The description in this paragraph is common to the first embodiment and the second embodiment.
[0377] In order to easily improve the resolution and contrast of an image, the internal haze of the optical film is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.
[0378] The internal haze can be measured by a general method. For example, the internal haze can be measured by laminating a transparent sheet or the like to the first surface of the optical film via a transparent adhesive layer to flatten the irregularities on the first surface.
[0379] The description in this paragraph is common to the first embodiment and the second embodiment.
[0380] Regarding the transmission image clarity of optical films measured in accordance with JIS K7374:2007, the transmission image clarity when the width of the optical comb is 0.125 mm is defined as C 0.125 , the clarity of the transmitted image with a comb width of 0.25 mm is defined as C 0.25, the clarity of the transmitted image with a comb width of 0.5 mm is defined as C 0.5 , the transmission image clarity with a comb width of 1.0 mm is defined as C 1.0 , the clarity of the transmitted image with a comb width of 2.0 mm is defined as C 2.0 When C 0.125 , C 0.25 , C 0.5 , C 1.0 and C 2.0 The value of is preferably in the range described below.
[0381] In order to achieve good anti-glare performance, C 0.125 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 0.125 It is preferably 1.0% or more. 0.125 The range of % may be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, or 1.0% to 20%.
[0382] In order to achieve good anti-glare performance, C 0.25 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 0.25 It is preferably 1.0% or more. 0.25 The range of % may be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, or 1.0% to 20%.
[0383] In order to achieve good anti-glare performance, C 0.5 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 0.5 It is preferably 1.0% or more. 0.5 The range of % may be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, or 1.0% to 20%.
[0384] In order to achieve good anti-glare performance, C 1.0 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 1.0 It is preferably 1.0% or more. 1.0 The range of % may be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, or 1.0% to 20%.
[0385] In order to achieve good anti-glare performance, C 2.0 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 2.0 It is preferably 5.0% or more. 2.0 The range of % may be 5.0% to 50%, 5.0% to 40%, 5.0% to 30%, or 5.0% to 20%.
[0386] The description in this paragraph is common to the first embodiment and the second embodiment.
[0387] In order to achieve good anti-glare properties, the C 0.125 , C 0.5 , C 1.0 and C 2.0 The total is preferably 200% or less, more preferably 150% or less, more preferably 100% or less, and more preferably 80% or less. In order to achieve good resolution, the total is preferably 10.0% or more. As the range of the total, 10.0% or more and 200% or less, 10.0% or more and 150% or less, 10.0% or more and 100% or less, and 10.0% or more and 80% or less can be listed.
[0388] The description in this paragraph is common to the first embodiment and the second embodiment.
[0389] <Size, shape, etc.>
[0390] The optical film may be in the form of a single sheet cut into a predetermined size, or in the form of a roll in which a long sheet is rolled up. The size of the single sheet is not particularly limited, but the maximum diameter is about 2 inches or more and 500 inches or less. The "maximum diameter" refers to the maximum length when any two points of the optical film are connected. For example, when the optical film is rectangular, the diagonal of the area becomes the maximum diameter. When the optical film is circular, the diameter of the circle becomes the maximum diameter.
[0391] The width and length of the roll are not particularly limited, but generally the width is 500 mm to 3000 mm, and the length is about 500 m to 5000 m. The optical film in a roll form can be cut into a single piece for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll with unstable physical properties.
[0392] The shape of the single piece is not particularly limited, and for example, polygons such as triangles, quadrilaterals, and pentagons, circles, random amorphous shapes, etc. can be listed. More specifically, when the optical film is a quadrilateral, the aspect ratio is not particularly limited as long as there is no problem as a display screen. For example, horizontal:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, etc. can be listed, but in the design-rich vehicle-mounted use or digital signage use, it is not limited to such an aspect ratio.
[0393] The surface shape of the second surface of the optical film is not particularly limited, but is preferably substantially smooth. Substantially smooth means that the arithmetic mean roughness Ra of JIS B0601:1994 at a cutoff value of 0.8 mm is less than 0.03 μm, preferably 0.02 μm or less.
[0394] The description in this paragraph is common to the first embodiment and the second embodiment.
[0395] [Method for producing optical film according to first embodiment]
[0396] The method for producing an optical film according to the first embodiment of the present disclosure is the above-mentioned method for producing an optical film according to the present disclosure, and includes a first step of forming an antiglare layer on a substrate, and a second step of forming an antireflection layer on the antiglare layer.
[0397] Examples of means for forming the antiglare layer on the substrate include the above-mentioned (A) method using an embossing roll, (B) etching treatment, (C) molding using a mold, and (D) coating film formation by coating.
[0398] In the case of method (A), for example, a resin layer is formed on a substrate, and then shaped from the resin layer side using an embossing roll, whereby an anti-glare layer can be formed on the substrate.
[0399] In the case of method (B), for example, by forming a layer of a photocurable resin on a substrate and performing photoetching, an antiglare layer can be formed on the substrate.
[0400] In the case of the method (C), for example, the anti-glare layer can be formed on the substrate by pouring the resin into a mold, taking out the molded resin from the mold, and placing it on the substrate.
[0401] In the case of the method (D), for example, by forming a coating film on a substrate using the method (d1) or (d2) described above, an antiglare layer can be formed on the substrate.
[0402] As a means for forming the antireflection layer on the antiglare layer, for example, the above-mentioned wet method or dry method can be mentioned.
[0403] [Polarizing plate according to the first embodiment]
[0404] A polarizing plate according to a first embodiment of the present disclosure includes a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer.
[0405] At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to the first embodiment of the present disclosure, and the second surface of the optical film is arranged to face the polarizer.
[0406] <Polarizer>
[0407] Examples of polarizers include sheet-type polarizers such as polyvinyl alcohol films, polyvinyl formal films, polyvinyl acetal films, and ethylene-vinyl acetate copolymer saponified films dyed with iodine or the like and stretched; wire grid polarizers composed of a plurality of metal wires arranged in parallel; coating polarizers coated with lyotropic liquid crystal or dichroic guest-host materials; and multilayer film polarizers. These polarizers may also be reflective polarizers that have the function of reflecting non-transmitted polarized light components.
[0408] The description in this paragraph is common to the first embodiment and the second embodiment.
[0409] <Transparent protective plate>
[0410] A first transparent protective plate is disposed on one side of the polarizer, and a second transparent protective plate is disposed on the other side. At least one of the first transparent protective plate and the second transparent protective plate is the optical film of the first embodiment of the present disclosure described above.
[0411] In the polarizing plate of the present disclosure, one of the first transparent protective plate and the second transparent protective plate may be the optical film of the first embodiment of the present disclosure, or both of the first transparent protective plate and the second transparent protective plate may be the optical film of the first embodiment of the present disclosure.
[0412] As the transparent protective plate that is not the optical film of the first embodiment of the present disclosure among the first transparent protective plate and the second transparent protective plate, a general-purpose plastic film, glass, or the like can be used.
[0413] The polarizer and the transparent protective plate are preferably bonded together via an adhesive. As the adhesive, a general-purpose adhesive can be used, and a PVA-based adhesive is preferred.
[0414] [Surface panel for image display device according to first embodiment]
[0415] The surface plate for an image display device of the first embodiment of the present disclosure is a surface plate for an image display device formed by laminating a protective film on a resin plate or a glass plate, wherein the protective film is the optical film of the first embodiment of the present disclosure mentioned above, and the second surface of the optical film is arranged opposite to the resin plate or the glass plate.
[0416] As the resin plate or the glass plate, a resin plate or a glass plate generally used as a surface plate of an image display device can be used.
[0417] In order to achieve good strength, the thickness of the resin plate or glass plate is preferably 10 μm or more. The upper limit of the thickness of the resin plate or glass plate is usually 5000 μm or less. In order to achieve thinness, the upper limit of the thickness of the resin plate or glass plate is preferably 1000 μm or less, more preferably 500 μm or less, and further preferably 100 μm or less.
[0418] Examples of the thickness range of the resin plate or the glass plate include 10 μm to 5000 μm, 10 μm to 1000 μm, 10 μm to 500 μm, and 10 μm to 100 μm.
[0419] The description in this paragraph is common to the first embodiment and the second embodiment.
[0420] [Image Display Panel of First Embodiment]
[0421] The image display panel of the first embodiment of the present disclosure comprises a display element and an optical film arranged on the light emitting surface side of the display element, wherein the image display panel includes the optical film of the first embodiment of the present disclosure as the optical film (refer to Figure 2 ).
[0422] In the image display panel, the optical film according to the first embodiment of the present disclosure is preferably arranged so that the second surface side faces the display element side.
[0423] In the image display panel, the optical film according to the first embodiment of the present disclosure is preferably disposed on the outermost surface on the light emitting surface side of the display element.
[0424] As display elements, liquid crystal display elements, EL display elements (organic EL display elements, inorganic EL display elements), plasma display elements, etc., and LED display elements such as micro LED display elements can be listed. These display elements can also have a touch panel function inside the display element.
[0425] Examples of a display method of liquid crystal in a liquid crystal display element include an IPS method, a VA method, a multi-domain method, an OCB method, a STN method, and a TSTN method.
[0426] Furthermore, the image display panel of the present disclosure may be an image display panel with a touch panel having a touch panel between a display element and an optical film.
[0427] The size of the image display panel is not particularly limited, but the maximum diameter is about 2 inches or more and 500 inches or less. The maximum diameter refers to the maximum length when connecting any two points in the plane of the image display panel.
[0428] The description in this paragraph is common to the first embodiment and the second embodiment.
[0429] [Image Display Device According to First Embodiment]
[0430] An image display device according to a first embodiment of the present disclosure includes the image display panel according to the first embodiment of the present disclosure.
[0431] The image display device of the first embodiment of the present disclosure is not particularly limited as long as it includes the image display panel of the first embodiment of the present disclosure. The image display device of the first embodiment of the present disclosure preferably includes the image display panel of the first embodiment of the present disclosure, a drive control unit electrically connected to the image display panel, and a housing for accommodating them.
[0432] When the display element is a liquid crystal display element, a backlight is required in the image display device of the present disclosure. The backlight is arranged on the side of the liquid crystal display element opposite to the light emitting surface side.
[0433] The size of the image display device is not particularly limited, but the maximum diameter of the effective display area is approximately not less than 2 inches and not more than 500 inches.
[0434] The effective display area of the image display device is an area where an image can be displayed. For example, when the image display device has a casing surrounding a display element, the area inside the casing becomes the effective image area.
[0435] In addition, the maximum diameter of the effective image area refers to the maximum length when connecting any two points in the effective image area. For example, when the effective image area is a rectangle, the diagonal of the area becomes the maximum diameter. In addition, when the effective image area is a circle, the diameter of the area is the maximum diameter.
[0436] The description in this paragraph is common to the first embodiment and the second embodiment.
[0437] [Method for selecting optical film according to the first embodiment]
[0438] The method for selecting an optical film according to the first embodiment of the present disclosure selects an optical film that satisfies the following selection conditions.
[0439] (Optical film selection conditions)
[0440] The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0441] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0442] The first surface has a concavoconvex shape,
[0443] The arithmetic mean height Sa of the first surface as specified in ISO 25178-2:2012 is 0.05 μm or more,
[0444] The first surface satisfies the following formula 1,
[0445] Sw×Vmp≤2.00(Formula 1),
[0446] In Formula 1, "Sw" is the inclination angle (degrees) when a 30 μl drop of pure water flows down on the first surface, and "Vmp" is the protruding peak solid volume (ml / m2) of the first surface as specified in ISO 25178-2:2012. 2 ) value.
[0447] The method for selecting an optical film according to the first embodiment of the present disclosure may include additional selection conditions. As the additional selection conditions, preferred embodiments of the optical film according to the first embodiment can be listed. As the additional selection conditions, for example, the following A to D can be listed.
[0448] A: Vmp is 0.005ml / m 2 Above and 0.100ml / m 2 the following.
[0449] B: The optical film includes the antireflection layer, the antiglare layer, and a substrate in this order from the first surface toward the second surface.
[0450] C: The element ratio satisfies the following formulas 2 to 4.
[0451] 3.5≤F / inorganic Si≤10.0 (Formula 2),
[0452] 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3),
[0453] 5.0≤F / organic Si≤50.0 (Formula 4),
[0454] D: Total light reflectance R measured by the following method SCI Below 3.0%,
[0455] [Total light reflectance (R SCI )]
[0456] A sample was prepared in which a black plate was bonded to the second surface of the optical film via a transparent adhesive. The total light reflectance (R SCI ).
[0457] According to the method for selecting an optical film according to the first embodiment of the present disclosure, an optical film having excellent anti-glare properties and good fingerprint wiping properties can be efficiently selected.
[0458] [Optical film of the second embodiment]
[0459] The optical film according to the second embodiment of the present disclosure is as follows.
[0460] An optical film having a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0461] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0462] The first surface has a concavoconvex shape,
[0463] The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 above,
[0464] The falling contact angle measured by the following method is 30.0 degrees or more,
[0465] <Measurement of drop contact angle>
[0466] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0467] Figure 4 It is a schematic cross-sectional view of the cross-sectional shape of the optical film 100 according to the second embodiment of the present disclosure.
[0468] Figure 4 The optical film 100 has: a first surface having a concavoconvex shape; and a second surface which is a surface opposite to the first surface. Figure 4 In the figure, the upper surface is the first surface, and the lower surface is the second surface.
[0469] Figure 4 The optical film includes an antireflection layer 30, an antiglare layer 20, and a substrate 10 in this order from the first surface toward the second surface.
[0470] Figure 4 That is, the scale of each layer constituting the optical film 100 and the scale of the concavo-convex shape are schematically shown for ease of illustration and are different from the actual scale. Figure 5 That's the same.
[0471] The optical film of the second embodiment of the present disclosure is not limited to Figure 1 For example, the optical film of the second embodiment of the present disclosure may also be a laminated structure without a substrate. The optical film of the second embodiment of the present disclosure may also have layers other than the substrate, the anti-glare layer, and the anti-reflection layer.
[0472] <Page 1>
[0473] The optical film according to the second embodiment of the present disclosure has a first surface. In the optical film according to the second embodiment of the present disclosure, it is preferable that the surface of the antireflection layer is the first surface.
[0474] The first surface of the optical film of the second embodiment has a concavoconvex shape, and the protruding valley space volume Vvv specified in ISO 25178-2:2012 is 0.005 ml / m 2 When the first surface does not have a concavo-convex shape, the anti-glare property of the optical film cannot be improved. By making the first surface have a concavo-convex shape and making Vvv 0.005 ml / m 2 As described above, the anti-glare property of the optical film can be easily improved by this.
[0475] Vvv is preferably 0.007 ml / m 2 More preferably 0.010 ml / m 2 More preferably 0.020 ml / m 2 More preferably, 0.030 ml / m 2 above.
[0476] If Vvv is too large, it tends to be difficult to make the falling contact angle 30.0 degrees or more. Therefore, Vvv is preferably 0.100 ml / m 2 Below, more preferably 0.080ml / m 2 Below, more preferably 0.060ml / m 2 Below, more preferably 0.045 ml / m 2 the following.
[0477] Regarding the embodiment of the range of Vvv of the first surface, 0.005 ml / m 2 Above and 0.100ml / m 2 Below, 0.005ml / m 2 Above and 0.080ml / m2 Below, 0.005ml / m 2 Above and 0.060ml / m 2 Below, 0.005ml / m 2 Above 0.045ml / m 2 Below, 0.007ml / m 2 Above and 0.100ml / m 2 Below, 0.007ml / m 2 Above and 0.080ml / m 2 Below, 0.007ml / m 2 Above and 0.060ml / m 2 Below, 0.007ml / m 2 Above 0.045ml / m 2 Below, 0.010ml / m 2 Above and 0.100ml / m 2 Below, 0.010ml / m 2 Above and 0.080ml / m 2 Below, 0.010ml / m 2 Above and 0.060ml / m 2 Below, 0.010ml / m 2 Above 0.045ml / m 2 Below, 0.020ml / m 2 Above and 0.100ml / m 2 Below, 0.020ml / m 2 Above and 0.080ml / m 2 Below, 0.020ml / m 2 Above and 0.060ml / m 2 Below, 0.020ml / m 2 Above 0.045ml / m 2 Below, 0.030ml / m 2 Above and 0.100ml / m 2 Below, 0.030ml / m 2 Above and 0.080ml / m 2 Below, 0.030ml / m 2 Above and 0.060ml / m 2 Below, 0.030ml / m 2 Above 0.045ml / m 2 the following.
[0478] The first surface of the optical film according to the second embodiment has a drop contact angle of 30.0 degrees or more as measured by the method described below.
[0479] <Measurement of drop contact angle>
[0480] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0481] By setting the drop contact angle of the first surface to 30.0 degrees or more, the fingerprint wiping property can be easily improved. The relationship between the drop contact angle and the fingerprint wiping property is described below.
[0482] In the measurement of the drop contact angle disclosed in the present invention, a droplet is dropped from a height of 45 mm relative to the first surface of the optical film. The droplet dropped onto the first surface becomes a crushed shape due to the impact when dropped, so there is a tendency for the contact angle of the droplet just after it drops to become smaller. In particular, in the case of an optical film having a concave-convex shape with a Vvv of a predetermined value or more, the droplet is easily wetted and spread, so the contact angle of the droplet just after it drops tends to become smaller.
[0483] On the first surface of the optical film, the liquid in a crushed shape is difficult to wipe off. In the measurement of the drop contact angle of the present disclosure, the static contact angle 10 seconds after landing is measured by the θ / 2 method. Moreover, the drop contact angle of the optical film of the present disclosure is 30.0 degrees or more. That is, the optical film of the second embodiment of the present disclosure having a drop contact angle of 30.0 degrees or more means that the droplet that has become crushed due to the impact when falling recovers to a shape close to a spherical shape. Therefore, for the optical film of the second embodiment of the present disclosure, although having a Vvv of 0.005 ml / m 2 The above concavo-convex shape can also make the fingerprint wiping property good.
[0484] If you touch the surface of the optical film with your finger, the fingerprint components will penetrate into the inside of the concavo-convex shape due to the pressure of the touch. In the measurement of the drop contact angle disclosed in the present invention, the reason for dropping the droplet from a height of 45 mm is because the aforementioned phenomenon (the phenomenon that the fingerprint components penetrate into the inside of the concavo-convex shape due to pressure) is taken into consideration.
[0485] In the measurement of the falling contact angle, the amount of the dropped droplet was 5.0 μl.
[0486] Fingerprints contain not only water but also sebum and the like. Therefore, in the measurement of the falling contact angle of the present disclosure, a liquid having a surface tension of 30 mN / m is used instead of pure water. In this specification, as a liquid having a surface tension of 30 mN / m, a liquid having the following composition is used. In this specification, the surface tension refers to a value measured using a Wilhelmy surface tensiometer specified in JIS K2241:2017.
[0487] <Composition of liquid with surface tension of 30 mN / m>
[0488] It is a liquid containing 100% by mass of ethylene glycol monoethyl ether.
[0489] The falling contact angle is preferably 40.0 degrees or more, more preferably 45.0 degrees or more, and further preferably 50.0 degrees or more.
[0490] When the drop contact angle is too large, the content of the fluorine compound and the organosilicon compound in the antireflection layer increases, and the scratch resistance of the optical film is easily reduced. Therefore, the drop contact angle is preferably 70.0 degrees or less, more preferably 60.0 degrees or less, and further preferably 55.0 degrees or less.
[0491] Regarding the implementation method of the range of the falling contact angle of the first surface, there can be listed 30.0 degrees or more and 70.0 degrees or less, 30.0 degrees or more and 60.0 degrees or less, 30.0 degrees or more and 55.0 degrees or less, 40.0 degrees or more and 70.0 degrees or less, 40.0 degrees or more and 60.0 degrees or less, 40.0 degrees or more and 55.0 degrees or less, 45.0 degrees or more and 70.0 degrees or less, 45.0 degrees or more and 60.0 degrees or less, 45.0 degrees or more and 55.0 degrees or less, 50.0 degrees or more and 70.0 degrees or less, 50.0 degrees or more and 60.0 degrees or less, and 50.0 degrees or more and 55.0 degrees or less.
[0492] The pure water contact angle of the first surface of the optical film according to the second embodiment of the present disclosure is preferably 100 degrees or more and 120 degrees or less, and more preferably 110 degrees or more and 115 degrees or less.
[0493] In the second embodiment, the ratio of Vvv of the first surface of the optical film of the present disclosure to the core space volume Vvc specified by ISO 25178-2:2012 (Vvv / Vvc) is preferably 0.10 or less. By setting Vvv / Vvc to 0.10 or less, fingerprint wiping properties can be easily improved. Vvv / Vvc is more preferably 0.09 or less, and further preferably 0.08 or less.
[0494] In the second embodiment, with respect to the first surface of the optical film of the present disclosure, it is preferred that the protruding peak solid volume Vmp specified in ISO 25178-2:2012 is 0.005 ml / m 2 Above and 0.100ml / m 2 the following.
[0495] By making the Vmp of the first surface 0.005 ml / m 2More preferably, Vmp is 0.007 ml / m 2 More preferably 0.010 ml / m 2 More preferably 0.020 ml / m 2 above.
[0496] By setting the Vmp of the first surface to 0.100 ml / m 2 Below, the scratch resistance of the optical film can be easily improved. Vmp is more preferably 0.080 (ml / m 2 ) or less, more preferably 0.060 (ml / m 2 ) or less, more preferably 0.045 (ml / m 2 )the following.
[0497] In the second embodiment, regarding the first surface of the optical film of the present disclosure, it is preferred that the minimum autocorrelation length Sal specified in ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.
[0498] By setting Sal to 4.0 μm or more, fingerprint wiping properties can be easily improved, and by setting Sal to 12.0 μm or less, anti-glare properties can be easily improved.
[0499] The lower limit of Sal is more preferably 5.0 μm or more, and further preferably 6.0 μm or more. The upper limit of Sal is more preferably 11.0 μm or less, and further preferably 10.0 μm or less.
[0500] In the second embodiment, the peak height Sxp of the first surface of the optical film of the present disclosure as defined in ISO 25178-2:2012 is preferably 0.15 μm or more and 2.00 μm or less.
[0501] Sxp is a parameter representing the difference between the average surface of the concavo-convex shape and the convex portion after removing the particularly high convex portion in the concavo-convex shape. By setting Sxp to 0.15 μm or more, it is easy to make the anti-glare property good. By setting Sxp to 2.00 μm or less, it is easy to make the fingerprint wiping property better.
[0502] The lower limit of Sxp is more preferably 0.20 μm or more, more preferably 0.25 μm or more, more preferably 0.50 μm or more, and more preferably 0.70 μm or more. The upper limit of Sxp is more preferably 1.80 μm or less, more preferably 1.50 μm or less, and more preferably 1.40 μm or less.
[0503] Regarding the implementation of the range of Sxp of the first surface, there can be listed 0.15 μm or more and 2.00 μm or less, 0.15 μm or more and 1.80 μm or less, 0.15 μm or more and 1.50 μm or less, 0.15 μm or more and 1.40 μm or less, 0.20 μm or more and 2.00 μm or less, 0.20 μm or more and 1.80 μm or less, 0.20 μm or more and 1.50 μm or less, 0.20 μm or more and 1.40 μm or less, 0.25 μm or more and 2.00 μm or less, 0.25 μm or more and 0.25 μm or more Above and below 1.80μm, above 0.25μm and below 1.50μm, above 0.25μm and below 1.40μm, above 0.50μm and below 2.00μm, above 0.50μm and below 1.80μm, above 0.50μm and below 1.50μm, above 0.50μm and below 1.40μm, above 0.70μm and below 2.00μm, above 0.70μm and below 1.80μm, above 0.70μm and below 1.50μm, above 0.70μm and below 1.40μm.
[0504] In the second embodiment, regarding the optical film of the present disclosure, it is preferred that the element ratios obtained by analyzing the surface region on the first surface side by X-ray photoelectron spectroscopy satisfy the following Formulae 2 to 4.
[0505] 3.5≤F / inorganic Si≤10.0 (Formula 2),
[0506] 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3),
[0507] 5.0≤F / organic Si≤50.0 (Formula 4),
[0508] In Formulae 2 to 4, "F" is the ratio of fluorine element, "inorganic Si" is the ratio of silicon element belonging to the inorganic silicon compound, and "organic Si" is the ratio of silicon element belonging to the organic silicon compound.
[0509] In the surface region of the first surface of the optical film, inorganic Si can reduce the refractive index of the first surface, but on the other hand, there is a tendency to deteriorate the fingerprint wiping property. In addition, by including a predetermined amount or more of organic Si and F relative to inorganic Si in the surface region of the first surface of the optical film, there is a tendency to improve the fingerprint wiping property. Furthermore, by including organic Si and F in a well-balanced manner in the surface region of the first surface of the optical film, there is a tendency to improve the fingerprint wiping property. Therefore, by making F / inorganic Si greater than 3.5, and making organic Si / inorganic Si greater than 0.08, and making F / organic Si greater than 5.0 and less than 50.0, it is easy to make the drop contact angle greater than 30.0 degrees, and it is easy to improve the fingerprint wiping property.
[0510] Furthermore, by setting F / inorganic Si to 10.0 or less and organic Si / inorganic Si to 1.00 or less, it is possible to easily suppress a decrease in the coating properties of the antireflection layer.
[0511] The preferred embodiments of F / inorganic Si, organic Si / inorganic Si, and F / organic Si are as described above.
[0512] The embodiment of the range of the ratio of inorganic Si to all elements in the surface region of the first surface of the optical film is as described above.
[0513] <Layered Structure>
[0514] The optical film of the second embodiment of the present disclosure includes an antireflection layer and an antiglare layer in this order from the first surface toward the second surface. The outermost surface of the first surface side of the optical film of the second embodiment is preferably an antireflection layer.
[0515] As described above, the optical film of the present disclosure may have layers other than the antireflection layer and the antiglare layer. Embodiments of the layers other than the antireflection layer and the antiglare layer are as described above.
[0516] Substrate
[0517] For ease of production and ease of handling, the optical film of the second embodiment preferably has a substrate.
[0518] The material of the substrate, the composition of the substrate, the thickness of the substrate, the total light transmittance of the substrate, the haze of the substrate, and the surface treatment of the substrate are as described above.
[0519] Anti-glare layer
[0520] In the second embodiment, the anti-glare layer is a layer that plays a central role in anti-glare properties.
[0521] In the second embodiment, the anti-glare layer can be formed by, for example, (A) a method using an embossing roller, (B) etching treatment, (C) molding based on a mold, (D) coating film formation based on coating, etc. In order to easily obtain a stable surface shape, the molding based on a mold of (C) is preferred, and in order to improve productivity and cope with multiple varieties, the coating film formation based on coating of (D) is preferred.
[0522] In the method of (C), for example, by allowing the resin to flow into a mold and taking the molded resin out of the mold, an anti-glare layer can be formed. The molded resin taken out of the mold can be arranged on a substrate. For the mold, a mold that reverses the surface shape of the anti-glare layer is used. Such a mold can be made, for example, by the following methods (c1-1) to (c1-2) or the following method (c2).
[0523] (c1-1) Create a shape in which Vvv and the like fall within a predetermined range through simulation. Then, invert the simulated shape.
[0524] (c1-2) The surface of the metal is engraved with a laser or processed with photolithography so that the inverted shape is reflected, thereby obtaining a mold.
[0525] (c2) A mold having a shape reversed from that of the anti-glare layer produced in (D) is obtained by a general electroforming method.
[0526] When the anti-glare layer is formed by (D), for example, the following methods (d1) and (d2) are mentioned. (d1) is preferred because the range of the surface shape such as Vvv can be more easily adjusted than (d2).
[0527] (d1) A method of applying and drying a coating liquid containing a binder resin and particles to form an anti-glare layer having unevenness due to the particles.
[0528] (d2) A method of forming projections and depressions by applying a coating liquid containing an arbitrary resin and a resin having poor compatibility with the above-mentioned resin, and causing the resin to phase separate.
[0529] -thickness-
[0530] The embodiment of the range of the thickness T of the anti-glare layer is as described above.
[0531] -Element-
[0532] As described above, the anti-glare layer preferably mainly contains a resin component. Furthermore, the anti-glare layer may contain the above-mentioned other components as necessary.
[0533] As described above, the antiglare layer preferably contains a binder resin and particles.
[0534] As for particles, organic particles and inorganic particles can be listed, preferably inorganic particles. That is, the anti-glare layer preferably comprises a binder resin and inorganic particles. In addition, the anti-glare layer more preferably comprises a binder resin, inorganic particles and organic particles.
[0535] - Particles -
[0536] The embodiments of the materials of the inorganic particles and the organic particles and the embodiments of the shapes of the inorganic particles and the organic particles are as described above unless otherwise specified.
[0537] Compared with spherical particles, amorphous inorganic particles have a tendency to easily increase Vvv and easily reduce Sal. However, if the particle size distribution of the amorphous inorganic particles is too wide, Vvv is easy to become large, so the fingerprint wipeability is easy to reduce. In particular, if the amorphous inorganic particles are condensed, Vvv becomes larger, and the fingerprint wipeability becomes easier to reduce. On the other hand, if the particle size distribution of the amorphous inorganic particles is too narrow, the coating adaptability is easy to reduce. Therefore, the volume-based cumulative distribution of the particle size of the amorphous inorganic particles is preferably in the range described later. However, if inorganic particles are used alone, aggregation is likely to occur. Therefore, in the second embodiment, in order to make Vvv the above range and easily make the fingerprint wipeability good, it is preferred to make the particle size distribution of the amorphous particles in the range described later and use organic particles.
[0538] In the second embodiment, regarding inorganic particles such as amorphous inorganic particles, it is preferred that the volume-based cumulative distribution d10 of particle size, the volume-based cumulative distribution d50 of particle size, and the volume-based cumulative distribution d90 of particle size satisfy the following relationships (1) and (2).
[0539] 1.5≤d50 / d10≤4.0 (1)
[0540] 1.0≤d90 / d50≤3.0 (2)
[0541] D50 / d10 being 1.5 or more means that the particle size distribution of the inorganic particles in the region below the average is wider. By setting d50 / d10 to more than 1.5, it is easy to give fine concavo-convex to the concavo-convex surface, so Sal can be easily reduced. By setting d50 / d10 to less than 4.0, it is possible to suppress the amount of inorganic particles buried in the anti-glare layer to increase, thereby improving the addition efficiency of the inorganic particles.
[0542] d90 / d50 being 1.0 or more means that the particle size distribution of the inorganic particles in the region where the particle size is above the average is wide. By setting d90 / d50 to 1.0 or more, Vvv can be easily increased and Sal can be easily increased. By setting d90 / d50 to 3.0 or less, Vvv can be easily suppressed from becoming too large and Sal from becoming too large.
[0543] The lower limit of d50 / d10 is more preferably 1.8 or more, and still more preferably 2.0 or more, and the upper limit is more preferably 3.5 or less, and still more preferably 3.0 or less.
[0544] The lower limit of d90 / d50 is more preferably 1.3 or more, and still more preferably 1.5 or more, and the upper limit is more preferably 2.5 or less, and still more preferably 2.0 or less.
[0545] The d10, d50, and d90 of inorganic particles such as amorphous inorganic particles can be measured by a laser diffraction method.
[0546] In the second embodiment, the volume-based cumulative distribution d50 of the particle size of inorganic particles such as amorphous inorganic particles is preferably 2.5 μm to 5.5 μm, more preferably 3.0 μm to 5.0 μm, and further preferably 3.3 μm to 4.7 μm.
[0547] By setting d50 to 2.5 μm or more, the number of inorganic particles can be suppressed from excessively increasing, so it is easy to suppress Sal from becoming too small. By setting d50 to 5.5 μm or less, the number of inorganic particles can be suppressed from excessively decreasing, so it is easy to suppress Sal from becoming too large. In addition, by suppressing the excessive decrease in the number of inorganic particles, it is easy to form valleys between particles, so it is easy to increase Vvv.
[0548] The embodiment of the range of the ratio of the thickness T of the anti-glare layer to the d50 of the inorganic particles such as amorphous inorganic particles (d50 / T) is as described above.
[0549] The embodiment of the range of the ratio of the thickness T of the anti-glare layer to the d90 of the inorganic particles such as amorphous inorganic particles (d90 / T) is as described above.
[0550] The embodiment of the content range of inorganic particles such as amorphous inorganic particles is as described above.
[0551] In the second embodiment, the content of the organic particles is preferably 1 to 25 parts by mass, more preferably 3 to 18 parts by mass, and further preferably 8 to 14 parts by mass, relative to 100 parts by mass of the binder resin.
[0552] By making the content of organic particles more than 1 part by mass, the aggregation of inorganic particles can be easily suppressed. In addition, by making the content of organic particles more than 1 part by mass, the number of organic particles can be suppressed from being excessively reduced, so that valleys can be easily formed between particles. Therefore, Vvv can be easily increased. It should be noted that if the number of particles decreases, Vmp tends to increase.
[0553] Since the particle size distribution of organic particles is relatively uniform, the tendency of Sal to become smaller becomes stronger when the content of organic particles increases. Therefore, by making the content of organic particles less than 25 parts by mass, it is possible to prevent Sal from becoming too small and easily make fingerprint wiping properties good.
[0554] In the second embodiment, the average particle diameter of the organic particles is preferably 1.0 μm or more and 5.0 μm or less, more preferably 1.2 μm or more and 3.0 μm or less, and further preferably 1.3 μm or more and 2.5 μm or less.
[0555] By making the average particle size of the organic particles greater than 1.0 μm, the number of organic particles can be suppressed from increasing excessively, so it is easy to suppress Sal from becoming too small. Therefore, by making the average particle size of the organic particles greater than 1.0 μm, it is easy to make the fingerprint wiping property good. By making the average particle size of the organic particles less than 5.0 μm, the number of organic particles can be suppressed from decreasing excessively, so it is easy to form valleys between the particles. Therefore, Vvv can be easily increased. It should be noted that if the number of particles decreases, Vmp tends to increase.
[0556] In the second embodiment, the organic particles preferably have a narrow particle size distribution. Specifically, in the second embodiment, the proportion of particles within the range of ±0.5 μm of the average particle size of the organic particles is preferably 80% by volume or more, more preferably 85% by volume or more, and even more preferably 90% or more of the total amount of the organic particles. By narrowing the particle size distribution of the organic particles, the organic particles of uniform particle size are densely arranged, thereby easily preventing Vvv from becoming too large.
[0557] Embodiments of the shape of the organic particles are as described above.
[0558] In the second embodiment, the ratio of the average particle size of the organic particles to the thickness of the anti-glare layer (average particle size of the organic particles / thickness of the anti-glare layer) is preferably 0.20 or more and 0.70 or less, more preferably 0.23 or more and 0.50 or less, and further preferably 0.25 or more and 0.35 or less. By making the average particle size of the organic particles / thickness of the anti-glare layer the above range, Vvv and Sal can be easily made the above range.
[0559] -Inorganic particles-
[0560] As described above, the anti-glare layer may further contain inorganic fine particles in addition to the binder resin and the particles.
[0561] The material and average particle size of the inorganic fine particles are as described above.
[0562] -Binder resin-
[0563] As described above, in order to facilitate good scratch resistance, the binder resin preferably contains a cured product of a thermosetting resin composition or a cured product of an ionizing radiation curable resin composition, or a cured product of a curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.
[0564] As described above, the binder resin may contain a thermoplastic resin within a range not hindering the effects of the present disclosure.
[0565] The embodiments of the cured product of the curable resin composition and the binder resin such as the thermoplastic resin are as described above unless otherwise specified.
[0566] In the second embodiment, when the binder resin includes a cured product of an ionizing radiation curable resin composition, the ionizing radiation curable resin composition preferably includes a polyfunctional (meth)acrylate monomer and a polyfunctional (meth)acrylate oligomer.
[0567] In the second embodiment, the mass ratio of the polyfunctional (meth)acrylate monomer to the polyfunctional (meth)acrylate oligomer is preferably 5:95 to 60:40, more preferably 20:80 to 60:40, and even more preferably 40:60 to 60:40.
[0568] By making the polyfunctional (meth)acrylate monomer into a predetermined ratio or more, the scratch resistance of the anti-glare layer can be easily improved.
[0569] By making the multifunctional (meth) acrylate oligomer more than the prescribed ratio, the viscosity of the anti-glare layer coating solution can be increased, particles can be easily suppressed from sinking to the bottom of the anti-glare layer, and the binder resin can be easily suppressed from flowing down between the convex portions based on the particles. Therefore, Vvv can be easily made to be more than the prescribed value, and Sal can be easily made to be less than the prescribed value. On the other hand, if the proportion of the multifunctional (meth) acrylate oligomer is too much, the strength of the anti-glare layer can be reduced sometimes. In addition, if the viscosity of the anti-glare layer coating solution is too high, Vmp can become too large or Sal can become too small sometimes. Therefore, the ionizing radiation curable resin composition preferably includes a prescribed amount of multifunctional (meth) acrylate oligomer and a prescribed amount of multifunctional (meth) acrylate monomer.
[0570] -Solvents and drying conditions-
[0571] As described above, the anti-glare layer coating liquid preferably contains a solvent in order to adjust the viscosity or to dissolve or disperse the components.
[0572] Unless otherwise specified, the embodiments of the type and amount of the solvent to be blended are as described above.
[0573] In the second embodiment, the solvent in the anti-glare layer coating solution preferably has a solvent with a fast evaporation rate as the main component. By accelerating the evaporation rate of the solvent, it is possible to suppress the particles from sinking into the lower part of the anti-glare layer, and then it is easy to suppress the binder resin from flowing down between the convex parts based on the particles. Therefore, it is easy to make Vvv more than a specified value, and it is easy to make Sal less than a specified value.
[0574] In the second embodiment, when the anti-glare layer is formed from the anti-glare layer coating liquid, it is preferred to control the drying conditions.
[0575] The drying conditions can be controlled by the drying temperature and the wind speed in the dryer. The drying temperature is preferably 30° C. to 120° C., and the drying wind speed is preferably 0.2 m / s to 50 m / s. In addition, in order to control the surface shape of the anti-glare layer by drying, it is preferred to irradiate with ionizing radiation after the coating liquid is dried.
[0576] About drying conditions, preferably implement 2 stages of drying within the above-mentioned temperature range and wind speed range. And, preferably, compared with the drying in the first stage, in the drying in the second stage, make the drying temperature high temperature and make the wind speed enhanced. By slowly drying in the first stage, thus, when the binder resin covers the surface of the amorphous inorganic particles, the shape of the amorphous inorganic particles can be easily reflected on the surface of the binder resin. In addition, by making the drying temperature in the second stage higher than the drying temperature in the first stage and enhancing the wind speed, the agglomeration of organic particles can be easily suppressed, so the organic particles can be easily and densely configured. Therefore, by being set to the drying in two stages, thus, Vvv can be easily made to be more than a specified value, and Sal can be easily made to be less than a specified value.
[0577] In the first stage of drying, the drying temperature is preferably set to 30°C or more and less than 60°C, and the drying wind speed is preferably set to 0.2 m / s or more and less than 7 m / s. In the second stage of drying, the drying temperature is preferably set to 60°C or more and 120°C or less, and the drying wind speed is preferably set to 7 m / s or more and 50 m / s or less.
[0578] Anti-reflective layer
[0579] In the second embodiment, the antireflection layer is preferably located on the outermost surface on the first surface side.
[0580] The structure of the antireflection layer, the method for forming the layers constituting the antireflection layer such as the low refractive index layer and the high refractive index layer, and the embodiments of the materials forming the low refractive index layer and the high refractive index layer are as described above unless otherwise specified.
[0581] The refractive index of the low refractive index layer, the thickness of the low refractive index layer, and the embodiment of the binder resin of the low refractive index layer are as described above.
[0582] In the second embodiment, the binder resin of the low refractive index layer may also include a thermoplastic resin. By including a thermoplastic resin as the binder resin, the viscosity of the coating liquid for the low refractive index layer is increased, and the coating liquid for the low refractive index layer is not easy to flow down between the convex portions of the anti-glare layer. Therefore, by including a thermoplastic resin as the binder resin, it is easy to make Vvv above a specified value, and it is easy to make Sal below a specified value. Furthermore, since it is easy for organic Si and fluorine to remain near the surface of the first surface, it is easy to satisfy the element ratios of Formulas 2 to 4. On the other hand, if the viscosity of the coating liquid for the low refractive index layer becomes too high, defects may sometimes occur on the surface of the anti-glare layer when the coating liquid for the anti-reflection layer is applied.
[0583] Due to the above-mentioned effects and coating film strength, the content of the thermoplastic resin is preferably 0.1% by mass to 3.0% by mass, more preferably 0.2% by mass to 1.5% by mass, and further preferably 0.3% by mass to 0.7% by mass, based on the total amount of the binder resin.
[0584] The embodiment of the kind and weight average molecular weight of the thermoplastic resin is as described above.
[0585] The embodiments of low refractive index particles such as hollow particles and solid particles are as described above unless otherwise specified.
[0586] The embodiments of the average primary particle size of the hollow particles and the solid particles and the content of the hollow particles and the solid particles are as described above.
[0587] In the second embodiment, in order to make it easier for the first surface to satisfy the element ratios of Formulae 2 to 4, the low refractive index layer preferably includes a leveling agent containing organic Si and fluorine.
[0588] The configuration of the leveling agent, the content of the leveling agent, and other embodiments are as described above.
[0589] As described above, the high refractive index layer is preferably arranged closer to the anti-glare layer side than the low refractive index layer.
[0590] Embodiments of the refractive index of the high refractive index layer, the thickness of the high refractive index layer, the binder resin of the high refractive index layer, the high refractive index particles, the average primary particle size of the high refractive index particles, and the content of the high refractive index particles are as described above.
[0591] When forming an anti-reflection layer such as a low refractive index layer and a high refractive index layer by a wet method, it is preferred to increase the viscosity of the anti-reflection layer coating liquid. By increasing the viscosity of the anti-reflection layer coating liquid, the anti-reflection layer coating liquid is not easy to flow down between the convex parts of the anti-glare layer. Therefore, even if the anti-reflection layer is formed on the anti-glare layer, the surface shape of the anti-glare layer can be easily maintained. Therefore, by appropriately increasing the viscosity of the anti-reflection layer coating liquid, Vvv can be easily made to be above a specified value, and Sal can be easily made to be below a specified value. Furthermore, since it is easy to make organic Si and fluorine remain near the surface of the first surface, it is easy to satisfy the element ratios of Formulas 2 to 4. For example, by adding a thermoplastic resin as a binder resin, or increasing the proportion of an oligomer as an ionizing radiation curable resin composition, or selecting a solvent with a high viscosity as a solvent, etc., the viscosity of the anti-reflection layer coating liquid can be increased.
[0592] On the other hand, if the viscosity of the antireflection layer coating liquid is excessively increased, defects may be generated on the surface of the antiglare layer when the antireflection layer coating liquid is applied.
[0593] Therefore, the viscosity of the antireflection layer coating liquid at 23° C. is preferably 0.1 mPa·s or more and 5.0 mPa·s or less.
[0594] Examples of the solvent of the antireflection layer coating liquid include the same solvents as those described in the embodiments of the solvent of the antiglare layer coating liquid.
[0595] When forming the antiglare layer from the antireflection layer coating liquid, it is preferable to control the drying conditions.
[0596] The drying conditions can be controlled by the drying temperature and the wind speed in the dryer. The drying temperature is preferably above 30°C and below 70°C, and the drying wind speed is preferably above 10m / s and below 30m / s. By setting the drying temperature to a low temperature, the viscosity of the anti-reflection layer coating liquid can be easily increased. In addition, by increasing the wind speed, the viscosity of the anti-reflection layer coating liquid can be quickly increased. Therefore, by drying the anti-reflection layer coating liquid at a relatively low temperature and a relatively strong wind speed, the anti-reflection layer coating liquid can be prevented from flowing down between the convex portions of the anti-glare layer. That is, by drying the anti-reflection layer coating liquid at a relatively low temperature and a relatively strong wind speed, the surface shape such as Vvv of the first surface can be easily made to be within the above-mentioned range, and Formulas 1 to 4 can be easily satisfied.
[0597] It is preferred that the irradiation with ionizing radiation is performed after the antireflection layer coating liquid is dried.
[0598] - In the case of a multi-layer structure with more than 3 layers -
[0599] The embodiments of the stacked structure of the antireflection layer having a structure of three or more layers and the thickness of each layer are as described above.
[0600] <Optical Characteristics>
[0601] The total light reflectance R of the optical film of the second embodiment measured by the following method is SCI It is preferably 3.0% or less.
[0602] [Total light reflectance (R SCI )]
[0603] A sample was prepared in which a black plate was bonded to the second surface of the optical film via a transparent adhesive. The total light reflectance (R SCI ).
[0604] By making R SCI The R of the optical film is 3.0% or less. Therefore, in an environment where light with strong illumination is not incident on the first surface, the black tone of the black display portion can be easily improved, and thus the contrast can be easily improved. SCI It is more preferably 2.5% or less, and even more preferably 2.0% or less. SCI The lower limit of is not particularly limited, but is usually 0.1% or more.
[0605] Usually, when R SCI When the R is set to 3.0% or less, the contrast of the reflectance between the part with fingerprint components and the part without fingerprint components becomes large, and the aesthetics of the optical film is likely to be greatly reduced. However, in the optical film of the present disclosure, the fingerprint wiping property is improved by increasing the drop contact angle, so even if R is set to SCI When the content is 3.0% or less, it is also possible to easily suppress a decrease in the appearance of the optical film.
[0606] R SCI This is the reflected light measured by applying light to the sample surface from all directions using an integrating sphere and closing the light trap corresponding to the direction of regular reflection.
[0607] R SCI Measuring device, measuring R SCI The implementation method of the sample used is as described above.
[0608] The total light transmittance of the optical film in accordance with JIS K7361-1:1997 is preferably within the above range. The haze of the optical film in accordance with JIS K7136:2000 is preferably within the above range. The internal haze of the optical film is preferably within the above range.
[0609] Regarding the transmission image clarity of optical films measured according to JIS K7374:2007, C 0.125 , C 0.25 , C 0.5 , C 1.0and C 2.0 The above range is preferred. 0.125 , C 0.5 , C 1.0 and C 2.0 The total of is preferably within the above range.
[0610] <Size, shape, etc.>
[0611] The size of the optical film, the shape of the optical film, and the surface shape of the second surface of the optical film are as described above.
[0612] [Method for producing optical film according to the second embodiment]
[0613] A method for producing an optical film according to a second embodiment of the present disclosure is the above-mentioned method for producing an optical film according to the present disclosure, and includes a first step of forming an antiglare layer on a substrate, and a second step of forming an antireflection layer on the antiglare layer.
[0614] Examples of means for forming the antiglare layer on the substrate include the above-mentioned (A) method using an embossing roll, (B) etching treatment, (C) molding using a mold, and (D) coating film formation by coating.
[0615] In the case of method (A), for example, a resin layer is formed on a substrate, and then shaped from the resin layer side using an embossing roll, whereby an anti-glare layer can be formed on the substrate.
[0616] In the case of method (B), for example, by forming a layer of a photocurable resin on a substrate and performing photoetching, an antiglare layer can be formed on the substrate.
[0617] In the case of the method (C), for example, the anti-glare layer can be formed on the substrate by pouring the resin into a mold, taking out the molded resin from the mold, and placing it on the substrate.
[0618] In the case of the method (D), for example, by forming a coating film on a substrate using the method (d1) or (d2) described above, an antiglare layer can be formed on the substrate.
[0619] As a means for forming the antireflection layer on the antiglare layer, for example, the above-mentioned wet method or dry method can be mentioned.
[0620] [Polarizing plate of the second embodiment]
[0621] The polarizing plate of the second embodiment of the present disclosure comprises a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical film of the second embodiment of the present disclosure mentioned above, and the second surface of the optical film is arranged opposite to the polarizer.
[0622] <Polarizer>
[0623] The embodiments of the polarizer are as described above.
[0624] <Transparent protective plate>
[0625] A first transparent protective plate is disposed on one side of the polarizer, and a second transparent protective plate is disposed on the other side. At least one of the first transparent protective plate and the second transparent protective plate is the optical film of the second embodiment of the present disclosure.
[0626] In the polarizing plate of the present disclosure, one of the first transparent protective plate and the second transparent protective plate may be the optical film of the second embodiment of the present disclosure, or both of the first transparent protective plate and the second transparent protective plate may be the optical film of the second embodiment of the present disclosure.
[0627] As the transparent protective plate that is not the optical film of the second embodiment of the present disclosure among the first transparent protective plate and the second transparent protective plate, a general-purpose plastic film, glass, or the like can be used.
[0628] The polarizer and the transparent protective plate are preferably bonded together via an adhesive. As the adhesive, a general-purpose adhesive can be used, and a PVA-based adhesive is preferred.
[0629] [Surface panel for image display device according to the second embodiment]
[0630] The surface plate for an image display device of the second embodiment of the present disclosure is a surface plate for an image display device formed by laminating a protective film on a resin plate or a glass plate, wherein the protective film is the optical film of the second embodiment of the present disclosure described above, and the second surface of the optical film is arranged opposite to the resin plate or the glass plate.
[0631] The embodiments of the resin plate or the glass plate are as described above.
[0632] [Image Display Panel of Second Embodiment]
[0633] The image display panel of the second embodiment of the present disclosure is an image display panel having a display element and an optical film arranged on the light emitting surface side of the display element, wherein the image display panel includes the optical film of the second embodiment of the present disclosure as the optical film (refer to Figure 5 ).
[0634] In the image display panel, the optical film according to the second embodiment of the present disclosure is preferably arranged so that the second surface side faces the display element side.
[0635] In the image display panel, the optical film according to the second embodiment of the present disclosure is preferably disposed on the outermost surface on the light emitting surface side of the display element.
[0636] The embodiment of the display element and the embodiment of the size of the image display panel are as described above. The embodiment of the image display panel with a touch panel is as described above.
[0637] [Image Display Device According to Second Embodiment]
[0638] An image display device according to a second embodiment of the present disclosure includes the image display panel according to the second embodiment of the present disclosure.
[0639] The image display device of the second embodiment of the present disclosure is not particularly limited as long as it includes the image display panel of the second embodiment of the present disclosure. The image display device of the second embodiment of the present disclosure preferably includes the image display panel of the second embodiment of the present disclosure, a drive control unit electrically connected to the image display panel, and a housing for accommodating them.
[0640] The embodiments of the backlight and the size of the image display device are as described above.
[0641] [Method for selecting optical film according to the second embodiment]
[0642] The method for selecting an optical film according to the second embodiment of the present disclosure selects an optical film that satisfies the following selection conditions.
[0643] (Optical film selection conditions)
[0644] The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0645] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0646] The first surface has a concavoconvex shape,
[0647] The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 above,
[0648] The falling contact angle measured by the following method is 30.0 degrees or more,
[0649] <Measurement of drop contact angle>
[0650] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0651] An image display panel including the present disclosure.
[0652] The method for selecting an optical film according to the second embodiment of the present disclosure may include additional selection conditions. As the additional selection conditions, preferred embodiments of the optical film according to the second embodiment may be listed. As the additional selection conditions, for example, the following A to D may be listed.
[0653] A: Vvv / Vvc is 0.10 or less.
[0654] B: The optical film includes the antireflection layer, the antiglare layer, and a substrate in this order from the first surface toward the second surface.
[0655] C: The element ratio satisfies the following formulas 2 to 4.
[0656] 3.5≤F / inorganic Si≤10.0 (Formula 2),
[0657] 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3),
[0658] 5.0≤F / organic Si≤50.0 (Formula 4),
[0659] D: Total light reflectance R measured by the following method SCI Below 3.0%,
[0660] [Total light reflectance (R SCI )]
[0661] A sample was prepared in which a black plate was bonded to the second surface of the optical film via a transparent adhesive. The total light reflectance (R SCI ).
[0662] According to the method for selecting an optical film according to the second embodiment of the present disclosure, an optical film having excellent anti-glare properties and good fingerprint wiping properties can be efficiently selected.
[0663] [Evaluation method for fingerprint wiping properties]
[0664] The fingerprint wiping property evaluation method of the present disclosure uses the value of the falling contact angle measured by the following measurement as an evaluation index.
[0665] <Measurement of drop contact angle>
[0666] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the surface of the object to be measured, and the droplet was dropped perpendicularly to the surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0667] According to the fingerprint wipe-off evaluation method disclosed in the present invention, the fingerprint wipe-off of the measurement object can be easily evaluated. Specifically, the smaller the value of the falling contact angle, the better the fingerprint wipe-off can be evaluated.
[0668] The present disclosure includes the following [1] to
[34] .
[0669] [1] An optical film comprising a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0670] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0671] The first surface has a concavoconvex shape,
[0672] The arithmetic mean height Sa of the first surface as specified in ISO 25178-2:2012 is 0.05 μm or more,
[0673] The first surface satisfies the following formula 1,
[0674] Sw×Vmp≤2.00(Formula 1),
[0675] In Formula 1, "Sw" is the inclination angle when a 30 μl drop of pure water flows down on the first surface, and in Formula 1, "Vmp" is the value of the protruding peak solid volume of the first surface specified by ISO 25178-2:2012. The unit of the inclination angle is degree, and the unit of the protruding peak solid volume is ml / m 2 .
[0676] [2] The optical film according to [1], wherein the Vmp of the first surface is 0.005 ml / m 2 Above and 0.100ml / m 2 the following.
[0677] [3] The optical film according to [1] or [2], wherein the first surface has a protruding valley portion space volume Vvv calculated as 80% of the load area ratio for separating the core portion and the protruding valley portion as specified in ISO 25178-2:2012, and is 0.005 ml / m 2 Above and 0.100ml / m 2 the following.
[0678] [4] The optical film according to [3], wherein the ratio of Vvv of the first surface to the core space volume Vvc specified by ISO 25178-2:2012 (Vvv / Vvc) is 0.10 or less.
[0679] [5] The optical film according to any one of [1] to [4], wherein the minimum autocorrelation length Sal of the first surface as specified in ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.
[0680] [6] The optical film according to any one of [1] to [5], wherein the optical film comprises the antireflection layer, the antiglare layer, and a substrate in this order from the first surface toward the second surface.
[0681] [7] The optical film according to any one of [1] to [6], wherein the anti-glare layer contains a binder resin and particles.
[0682] [8] The optical film according to any one of [1] to [6], wherein the element ratio of the optical film obtained by analyzing the surface region of the first surface side by X-ray photoelectron spectroscopy satisfies the following formulas 2 to 4:
[0683] 3.5≤F / inorganic Si≤10.0 (Formula 2),
[0684] 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3),
[0685] 5.0≤F / organic Si≤50.0 (Formula 4),
[0686] In Formulae 2 to 4, "F" is the ratio of fluorine element, "inorganic Si" is the ratio of silicon element belonging to the inorganic silicon compound, and "organic Si" is the ratio of silicon element belonging to the organic silicon compound.
[0687] [9] The optical film according to [8], wherein, in terms of the element ratios analyzed by the X-ray photoelectron spectroscopy, a ratio of inorganic Si to all elements is 2 atomic % or more and 20 atomic % or less.
[0688]
[10] The optical film according to any one of [1] to [9], wherein the total light reflectance R of the optical film measured by the following method is: SCI Below 3.0%,
[0689] [Total light reflectance R SCI Measurement of]
[0690] A sample was prepared by bonding a black plate to the second surface of the optical film via a transparent adhesive, and the total light reflectance R was measured with the optical film side of the sample as the light incident surface. SCI .
[0691]
[11] The optical film according to any one of [1] to
[10] , wherein the haze of the optical film according to JIS K7136:2000 is 20% or more and 75% or less.
[0692]
[12] A polarizing plate comprising a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein:
[0693] At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to any one of [1] to
[11] , and the second surface of the optical film is arranged to face the polarizer.
[0694]
[13] A surface plate for an image display device, which is formed by laminating a protective film on a resin plate or a glass plate, wherein the protective film is an optical film described in any one of [1] to
[11] , and the second surface of the optical film is arranged opposite to the resin plate or the glass plate.
[0695]
[14] An image display panel comprising a display element and an optical film arranged on a light emitting surface side of the display element, wherein the image display panel includes the optical film described in any one of [1] to
[11] as the optical film.
[0696]
[15] An image display device comprising the image display panel described in
[14] .
[0697]
[16] A method for producing an optical film, which is the method for producing an optical film according to any one of [1] to
[11] , wherein:
[0698] The optical film production method includes: a first step of forming an anti-glare layer on a substrate; and a second step of forming an anti-reflection layer on the anti-glare layer.
[0699]
[17] A method for selecting an optical film, the method comprising selecting an optical film that satisfies the following selection conditions:
[0700] (Optical film selection conditions)
[0701] The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0702] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0703] The first surface has a concavoconvex shape,
[0704] The arithmetic mean height Sa of the first surface as specified in ISO 25178-2:2012 is 0.05 μm or more,
[0705] The first surface satisfies the following formula 1,
[0706] Sw×Vmp≤2.00(Formula 1),
[0707] In Formula 1, "Sw" is the inclination angle when a 30 μl drop of pure water flows down on the first surface, and in Formula 1, "Vmp" is the value of the protruding peak solid volume of the first surface specified by ISO 25178-2:2012. The unit of the inclination angle is degree, and the unit of the protruding peak solid volume is ml / m 2 .
[0708]
[18] An optical film comprising a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0709] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0710] The first surface has a concavoconvex shape,
[0711] The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 above,
[0712] The falling contact angle measured by the following method is 30.0 degrees or more,
[0713] <Measurement of drop contact angle>
[0714] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0715]
[19] The optical film according to
[18] , wherein the ratio of Vvv of the first surface to the core space volume Vvc specified by ISO 25178-2:2012 (Vvv / Vvc) is 0.10 or less.
[0716]
[20] The optical film according to
[18] or
[19] , wherein the minimum autocorrelation length Sal of the first surface specified by ISO 25178-2:2012 is greater than or equal to 4.0 μm and less than or equal to 12.0 μm.
[0717]
[21] An optical film according to any one of
[18] to
[20] , wherein the pole height Sxp of the first surface is greater than 0.15 μm and less than 2.00 μm, and the pole height Sxp is defined by ISO 25178-2:2012 and refers to the difference between the height at a load area ratio of 2.5% and the height at a load area ratio of 50%.
[0718]
[22] The optical film according to any one of
[18] to
[21] , wherein the optical film has the antireflection layer, the antiglare layer, and the substrate in this order from the first surface toward the second surface.
[0719]
[23] The optical film according to any one of
[18] to
[22] , wherein the anti-glare layer contains a binder resin and particles.
[0720]
[24] The optical film according to any one of
[18] to
[23] , wherein the element ratio of the optical film obtained by analyzing the surface region of the first surface side by X-ray photoelectron spectroscopy satisfies the following formulas 2 to 4:
[0721] 3.5≤F / inorganic Si≤10.0 (Formula 2),
[0722] 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3),
[0723] 5.0≤F / organic Si≤50.0 (Formula 4),
[0724] In Formulae 2 to 4, "F" is the ratio of fluorine element, "inorganic Si" is the ratio of silicon element belonging to the inorganic silicon compound, and "organic Si" is the ratio of silicon element belonging to the organic silicon compound.
[0725]
[25] The optical film according to
[24] , wherein, with respect to the element ratios analyzed by the X-ray photoelectron spectroscopy, the ratio of inorganic Si to all elements is 2 atomic % or more and 20 atomic % or less.
[0726]
[26] The optical film according to any one of
[18] to
[25] , wherein the total light reflectance R of the optical film measured by the following method is SCI Below 3.0%,
[0727] [Total light reflectance R SCI Measurement of]
[0728] A sample was prepared by bonding a black plate to the second surface of the optical film via a transparent adhesive, and the total light reflectance R was measured with the optical film side of the sample as the light incident surface. SCI .
[0729]
[27] The optical film according to any one of
[18] to
[26] , wherein the haze of the optical film in JIS K7136:2000 is 20% or more and 75% or less.
[0730]
[28] A polarizing plate comprising a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein:
[0731] At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to any one of
[18] to
[27] , and the second surface of the optical film is arranged to face the polarizer.
[0732]
[29] A surface plate for an image display device, which is formed by laminating a protective film on a resin plate or a glass plate, wherein the protective film is an optical film described in any one of
[18] to
[27] , and the second surface of the optical film is arranged opposite to the resin plate or the glass plate.
[0733]
[30] An image display panel comprising a display element and an optical film arranged on the light emitting surface side of the display element, wherein the image display panel includes the optical film described in any one of
[18] to
[27] as the optical film.
[0734]
[31] An image display device comprising the image display panel described in
[30] .
[0735]
[32] A method for producing an optical film, which is the method for producing an optical film according to
[18] , wherein:
[0736] The optical film production method includes: a first step of forming an anti-glare layer on a substrate; and a second step of forming an anti-reflection layer on the anti-glare layer.
[0737]
[33] A method for selecting an optical film, the method comprising selecting an optical film that satisfies the following selection conditions:
[0738] (Optical film selection conditions)
[0739] The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein:
[0740] The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface.
[0741] The first surface has a concavoconvex shape,
[0742] The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 above,
[0743] The falling contact angle measured by the following method is 30.0 degrees or more,
[0744] <Measurement of drop contact angle>
[0745] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0746]
[34] A method for evaluating fingerprint wiping properties, wherein the value of the falling contact angle measured by the following measurement is used as an evaluation index,
[0747] <Measurement of drop contact angle>
[0748] A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the surface of the object to be measured, and the droplet was dropped perpendicularly to the surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
[0749] [Example]
[0750] Next, the present disclosure will be described in more detail by way of examples, but the present disclosure is not limited to these examples. In addition, "parts" and "%" are based on mass unless otherwise specified.
[0751] 《Examples and Comparative Examples of the First Embodiment》
[0752] 1. Measurement and evaluation
[0753] The optical films of the embodiments and comparative examples were measured and evaluated as follows. The atmosphere during each measurement and evaluation was: the temperature was 23±5°C, and the relative humidity was 40% to 65%. In addition, before each measurement and evaluation, the target sample was exposed to the atmosphere for 30 minutes to 60 minutes, and then the measurement and evaluation were performed. The results are shown in Table 1 or 2.
[0754] 1-1. Measurement of surface shape
[0755] The optical films of the examples and comparative examples were cut into 10 cm × 10 cm. The cut parts were selected from random parts after visually confirming that there were no abnormal points such as dirt and scratches. Sample 1 was prepared as follows: the substrate side of the cut optical film was bonded to a glass plate (thickness 2.0 mm) of 10 cm × 10 cm in length with the aid of an optically transparent adhesive sheet (trade name: Panaclean PD-S1, thickness 25 μm) from PANAC.
[0756] Using a confocal laser microscope (VK-X 250 (control unit), VK-X 260 (measurement unit)), after setting the sample 1 in a fixed and close contact state on the measurement stage, the surface shape of the first surface of each sample was measured and analyzed under the following measurement condition 1, image processing condition 1, and analysis condition 1. It should be noted that as the measurement / analysis software, a multi-file analysis application (version 1.3.1.120) was used.
[0757] (Measurement condition 1)
[0758] Laser wavelength: 408nm
[0759] Optical system for measurement: Confocal optical system
[0760] Objective lens: 150 times
[0761] Zoom: 1x
[0762] Measuring area: 93.95μm×70.44μm
[0763] Number of measurement points: 1024×768 points
[0764] Measurement conditions: Transparent surface shape / high precision / double scanning
[0765] (Image processing condition 1)
[0766] DCL / BCL: DCL=13000, BCL=65535, processing method: supplement from surrounding pixels
[0767] Height cut-off level: Strong
[0768] (Analysis condition 1)
[0769] Region: The entire region
[0770] Filter type: Gaussian
[0771] S-filter: 0.25μm
[0772] F-operation: plane tilt correction (area designation)
[0773] L-Filter: No
[0774] Terminal effect correction: ON
[0775] · s when calculating Sal: s = 0.20
[0776] · p, q when calculating Sxp: p = 2.5%, q = 50.0%
[0777] "Sa", "Vmp", "Vvv", "Vvc", "Sal", and "Sxp" of each measurement area are displayed by the analysis software and are used as measurement values.
[0778] 1-2. Contact angle
[0779] <Normal contact angle>
[0780] The optical films of the examples and comparative examples were cut into 10 cm squares. The substrate side of the cut optical film was bonded to a glass plate (10 cm long x 10 cm wide, 2.0 mm thick) with the aid of a transparent adhesive sheet to prepare a sample for measurement. For the cut portion, after visually confirming that there were no abnormal points such as dirt and scratches, the cut portion was selected from a random portion of the optical film. When bonding the optical film to the glass plate, the optical film was not wrinkled and no bubbles were allowed to enter between the optical film and the glass plate.
[0781] Using a contact angle meter (DM-300, Kyowa Interface Science Co., Ltd.), 1.0 μL of pure water was dropped on the first surface of each sample, and the static contact angle after 10 seconds of landing was measured by the θ / 2 method. A syringe with a fluororesin-coated needle was used for dropping pure water.
[0782] <Pure water falling angle>
[0783] The pure water drop inclination angle Sw of each sample was measured according to the steps (1) to (3) in the main text of the manual. A contact angle meter (product number "DMo-701" of the "DropMaster" series of Kyowa Interface Science Co., Ltd. and "SA-301" as an accessory) was used as the measuring device.
[0784] 1-3. Element ratio
[0785] The measuring sheets were cut out from the optical films of the embodiments and comparative examples. The X-ray photoelectron spectrometer was used to measure the X-ray photoelectron spectra of the C1s orbital, O1s orbital, Si2p orbital, and F1s orbital of the surface area of the first surface side of each measuring sheet under the following conditions. The peaks of each X-ray photoelectron spectra were separated to find the ratio of the F element and the Si element. In addition, the ratio of the Si element (inorganic Si) belonging to the inorganic silicon compound to the Si element (organic Si) belonging to the organic silicon compound was found from the X-ray photoelectron spectrum of the Si2p orbital.
[0786] <Measurement>
[0787] Device: "Kratos Nova" manufactured by Shimadzu Corporation
[0788] X-ray source: AlKα
[0789] X-ray output: 150W
[0790] Emission current: 10mA
[0791] Accelerating voltage: 15 kV
[0792] Measuring area: 300×700μm
[0793] Charge neutralization mechanism: ON
[0794] Pass energy (narrow spectrum measurement): 40eV
[0795] 1-4. Total light reflectance (R SCI )
[0796] The optical films of the examples and comparative examples were cut into 10 cm × 10 cm. The cut parts were selected from random parts after visually confirming that there were no abnormal points such as dirt and scratches. Sample 2 was prepared as follows: the substrate side of the cut optical film was attached to a black plate (Kuraray, trade name: Comoglass DFA2CG 502K (black), thickness 2 mm) with a size of 10 cm × 10 cm via an optically transparent adhesive sheet (trade name: Panaclean PD-S1) from PANAC.
[0797] The total light reflectance (R SCI ). The light source of the integrating sphere spectrophotometer is D65, the position of the light receiver is +8 degrees relative to the normal line of the sample, the opening angle of the light receiver is 10 degrees, the position of the light trap is -8 degrees relative to the normal line of the sample, and the viewing angle is 2 degrees.
[0798] 1-5. Haze (Hz)
[0799] The optical films of the examples and comparative examples were cut into 10 cm squares. The cut parts were selected from random parts after visually confirming that there were no abnormal points such as dirt and scratches. The haze of each sample according to JIS K7136:2000 was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory).
[0800] In order to stabilize the light source, wait for more than 15 minutes after turning on the power switch of the device, perform calibration without placing anything at the entrance opening, and then place the measurement sample at the entrance opening for measurement. Set the light incident surface to the substrate side.
[0801] It should be noted that the total light transmittance of the optical films of Examples and Comparative Examples was 90% or more.
[0802] 1-6. Transmitted image clarity
[0803] The optical films of the embodiments and comparative examples were cut into 10 cm squares. The cut parts were selected from random locations after visually confirming that there were no abnormalities such as dirt and scratches. The image clarity of the sample was measured using an imaging meter (trade name: ICM-1T) manufactured by Suga Testing Instruments Co., Ltd. in accordance with JIS K7374:2007. The width of the optical comb was 5 widths: 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm. The light incident surface during measurement was set to the substrate side. C 0.125 , C 0.25 , C 0.5 , C 1.0 and C 2.0 The value of C 0.125 , C 0.5 , C 1.0 and C 2.0 The total values are shown in Table 2.
[0804] 1-7. Black tone
[0805] As the sample, sample 2 prepared in 1-4 was used. The sample was observed in the same manner as in 1-4 except that the observer's line of sight was changed to about 160 cm above the ground.
[0806] 20 subjects evaluated based on the following evaluation scores. There were 5 subjects in each age group from 20 to 50 years old. The average score of the 20 subjects was calculated and ranked according to the following criteria. It can be said that the higher the ranking of the following criteria, the better the black tone of the black display part.
[0807] <Evaluation score>
[0808] (1) No sense of whiteness but full sense of blackness: 3 points
[0809] (2) Although it is black, it feels slightly white: 2 points
[0810] (3) Noticed whiteness: 1 point
[0811] <Evaluation Criteria>
[0812] A: Average score is 2.5 or above
[0813] B: Average score is 2.0 or more and less than 2.5
[0814] C: Average score is 1.5 or more and less than 2.0
[0815] D: Average score less than 1.5
[0816] 1-8. Anti-glare
[0817] In a bright room environment, the sample 2 prepared in 1-4 was placed on a horizontal platform at a height of 70 cm with the concavo-convex surface facing upward. At this time, the sample was placed so as to be approximately directly below the illumination light. The sample was observed from the front (where the observer did not block the illumination light), and the reflection of the illumination light on the concavo-convex surface was evaluated according to the following evaluation criteria.
[0818] For lighting, a straight tube three-wavelength daylight fluorescent lamp of type Hf32 was used, and the lighting position was set at a height of 2m above the horizontal platform in the vertical direction. The evaluation was performed within the range of illuminance of 500 lux or more and 1000 lux or less on the concave and convex surface of the sample. The observer's line of sight was about 120cm from the ground. The observer was a healthy person in his 30s with a visual acuity of 0.7 or more.
[0819] <Evaluation Criteria>
[0820] A: There is no outline of the lighting and the location is unknown
[0821] B: No illuminated outline, but vaguely known location
[0822] C: vaguely aware of the outline and position of the lighting
[0823] D: The lighting outline is less ambiguous and the position is clearly visible
[0824] 1-9. Fingerprint wipeability
[0825] 0.1 ml of the following artificial dirt was allowed to permeate into the waste cloth. The permeation time was 10 seconds. As the waste cloth, a product named "absorbent wiping paper" manufactured by Nippon Paper Crecia Co., Ltd. was used.
[0826] 300g / cm 2 The artificial dirt that penetrated into the waste cloth was transferred to the surface of the rubber with a load of 300 g / cm. The shape of the rubber was a cylinder with a diameter of 12 mm. The transfer time was 5 seconds. 2 The artificial dirt transferred to the surface of the rubber was transferred to the first surface of sample 2 under a load of 1.000. The transfer time was 5 seconds. A spectrophotometer (manufactured by Konica Minolta, trade name: CM-600d) was used to measure the total light reflectance SCI L of the portion where the artificial dirt was transferred from the first surface of sample 2. * value, a * Value and b * The obtained L * Value, a * Value and b * The values are taken as L1, a1 and b1.
[0827] Next, the black plate side of sample 2 with artificial dirt transferred is attached to the base of the Gakushin wear tester (manufactured by TESTERSANGYO Co., Ltd., trade name "AB-301"). A waste cloth is mounted on the friction part of the tester, and the artificial dirt transferred to the first side of sample 2 is wiped off under the following wiping conditions. As for the waste cloth, a product with the trade name "ASPURE PROPREA II" produced by AS ONE was used. Using a spectrophotometer (manufactured by Konica Minolta, Ltd., trade name: CM-600d), the L of total light reflection SCI of the area after the artificial dirt is wiped off is measured from the first side of sample 2. * Value, a * Value and b * The obtained L * value, a * Value and b * The values are taken as L2, a2 and b2.
[0828] The color difference (ΔE) was calculated by the following formula, and the color difference values were ranked according to the following criteria. The higher the ranking according to the following criteria, the better the fingerprint wiping property is.
[0829] ΔE={(L1-L2) 2 +(a1-a2) 2 +(b1-b2) 2} 1 / 2
[0830] <Artificial Dirt>
[0831] It is a liquid containing about 45% by mass of oleic acid, about 25% by mass of triolein, about 20% by mass of oleic acid cholesterol, about 4% of liquid paraffin, about 4% of squalene, and about 2% of cholesterol (artificial dirt manufactured by ISEKUSHI Corporation (polluted liquid in accordance with JIS C9606:2007)).
[0832] <Wiping conditions>
[0833] Moving speed: 100mm / sec
[0834] Load: 150g / cm 2
[0835] Wipe times: 1 time per trip
[0836] <Evaluation Criteria>
[0837] A: Color difference is less than 2
[0838] B: Color difference is more than 2 and less than 4
[0839] C: Color difference is more than 4 and less than 7
[0840] D: Color difference exceeds 7
[0841] 1-10. Comprehensive evaluation
[0842] Based on the two evaluations of anti-glare property and fingerprint wiping property, comprehensive evaluation was performed according to the following criteria.
[0843] <Evaluation Criteria>
[0844] A: Both ratings are A.
[0845] B: One of the two evaluations is A and the other is B.
[0846] C: Both of the 2 evaluations were B.
[0847] D: At least one of the two ratings is C or D.
[0848] 2. Production of optical films
[0849] [Example 1-1]
[0850] The following anti-glare coating liquid 1-1 was applied on a substrate (triacetyl cellulose resin film with a thickness of 80 μm, manufactured by Fujifilm Corporation). Next, the coating liquid was dried at 50° C. and a wind speed of 2 m / s for 40 seconds, and further dried at 70° C. and a wind speed of 15 m / s for 45 seconds. Next, the coating liquid was dried in a nitrogen atmosphere with an oxygen concentration of 200 ppm or less at a cumulative light intensity of 50 mJ / cm 2 The anti-glare layer with a thickness of 5.5 μm was formed by irradiating ultraviolet rays in a manner.
[0851] Next, the anti-glare layer was coated with the following low refractive index layer coating liquid 1-1. Next, the anti-glare layer was dried at 40°C and a wind speed of 20 m / s for 15 seconds, and further dried at 70°C and a wind speed of 15 m / s for 30 seconds. Next, the anti-glare layer was dried in a nitrogen atmosphere with an oxygen concentration of 200 ppm or less at a cumulative light intensity of 150 mJ / cm 2 The low refractive index layer was irradiated with ultraviolet light in a manner of 0.10 μm thick to obtain an optical film of Example 1-1. The refractive index of the low refractive index layer was 1.31.
[0852] <Anti-glare layer coating liquid 1-1>
[0853] Polyurethane acrylate A 50 parts
[0854] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-1100H: molecular weight 800, number of functional groups 6)
[0855] · Polyurethane acrylate B 10 parts
[0856] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15)
[0857] · Pentaerythritol triacrylate 40 parts
[0858] (Toa Gosei Co., Ltd., trade name: M-305)
[0859] · 23 parts of silicon dioxide particles
[0860] (Surface treated amorphous silica, d10: 1.2μm, d50: 3.8μm, d90: 6.5μm)
[0861] · Organic particles B 8 parts
[0862] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5μm, refractive index 1.595)
[0863] · Photopolymerization initiator 5.0 parts
[0864] (IGM Resins BV, trade name: Omnirad184)
[0865] · Photopolymerization initiator 1.0 part
[0866] (IGM Resins BV, trade name: Omnirad907)
[0867] 0.1 part of silicone leveling agent
[0868] (Momentive Performance Materials, trade name: TSF 4460)
[0869] Solvent (toluene) 195 parts
[0870] Solvent (cyclohexanone) 5 parts
[0871] Solvent (methyl isobutyl ketone) 15 parts
[0872] <Low refractive index layer coating liquid 1-1>
[0873] ·Multifunctional acrylate 100 parts
[0874] (Toagosei Co., Ltd., trade name "Aronix M-400")
[0875] 0.5 parts of acrylic polymer (weight average molecular weight: 40,000)
[0876] ·180 parts of hollow silica particles
[0877] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[0878] 600 parts of fluorine-based silicone leveling agent with reactive functional groups
[0879] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[0880] · Photopolymerization initiator 5.0 parts
[0881] (IGM Resins, product name: Omnirad127)
[0882] Solvent (methyl isobutyl ketone) 11,000 parts
[0883] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[0884] [Examples 1-2, 1-3, 1-5, 1-6]
[0885] Optical films of Examples 1-2, 1-3, 1-5, and 1-6 were obtained in the same manner as in Example 1-1 except that the anti-glare layer coating liquid 1-1 was changed to the following anti-glare layer coating liquids 1-2 to 1-5.
[0886] [Examples 1-4]
[0887] An optical film of Example 1-4 was obtained in the same manner as in Example 1-1 except that the antiglare layer coating liquid 1-1 was changed to the following antiglare layer coating liquid 1-2 and the low refractive index layer coating liquid 1-1 was changed to the following low refractive index layer coating liquid 1-2.
[0888] [Examples 1-7]
[0889] An optical film of Example 1-7 was obtained in the same manner as in Example 1-1 except that the anti-glare layer coating liquid 1-1 was changed to the following anti-glare layer coating liquid 1-6 and the thickness of the anti-glare layer was changed to 4.8 μm.
[0890] [Examples 1-8]
[0891] An optical film of Example 1-8 was obtained in the same manner as in Example 1-1 except that the antiglare layer coating liquid 1-1 was changed to the following antiglare layer coating liquid 1-2 and the low refractive index layer coating liquid 1-1 was changed to the following low refractive index layer coating liquid 1-3. The refractive index of the low refractive index layer was 1.36.
[0892] [Comparative Example 1-1]
[0893] An optical film of Comparative Example 1-1 was obtained in the same manner as in Example 1-1 except that the low-refractive-index layer coating liquid 1-1 was changed to the following low-refractive-index layer coating liquid 1-4.
[0894] [Comparative Examples 1-2 to 1-3]
[0895] Optical films of Comparative Examples 1-2 to 1-3 were obtained in the same manner as in Comparative Example 1-1, except that the anti-glare layer coating liquid 1-1 was changed to the following anti-glare layer coating liquids 1-2 to 1-3.
[0896] [Comparative Examples 1-4]
[0897] An optical film of Comparative Example 1-4 was obtained in the same manner as in Example 1-1, except that the anti-glare layer coating liquid 1-1 was changed to the following anti-glare layer coating liquid 1-7 and the thickness of the anti-glare layer was changed to 5.0 μm.
[0898] <Anti-glare layer coating liquid 1-2>
[0899] Polyurethane acrylate A 50 parts
[0900] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-1100H: molecular weight 800, number of functional groups 6)
[0901] · Polyurethane acrylate B 10 parts
[0902] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15)
[0903] · Pentaerythritol triacrylate 40 parts
[0904] (Toa Gosei Co., Ltd., trade name: M-305)
[0905] · 21 parts of silica particles (surface treated amorphous silica, d10: 1.2 μm, d50: 3.8 μm, d90: 6.5 μm) · 10 parts of organic particles B (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.595) · 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[0906] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[0907] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[0908] Solvent (toluene) 185 parts
[0909] Solvent (cyclohexanone) 15 parts
[0910] Solvent (methyl isobutyl ketone) 15 parts
[0911] <Anti-glare layer coating liquid 1-3>
[0912] · Urethane acrylate A 50 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-1100H: molecular weight 800, number of functional groups 6) · Urethane acrylate B 10 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · Pentaerythritol triacrylate 40 parts (Toagosei Co., Ltd., trade name: M-305)
[0913] · 19 parts of silica particles (surface treated amorphous silica, d10: 1.2 μm, d50: 3.8 μm, d90: 6.5 μm) · 3 parts of organic particles A (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.515) · 5 parts of organic particles B (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.595) · 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[0914] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[0915] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[0916] Solvent (toluene) 165 parts
[0917] Solvent (cyclohexanone) 20 parts
[0918] Solvent (methyl isobutyl ketone) 30 parts
[0919] <Anti-glare layer coating liquid 1-4>
[0920] · Urethane acrylate A 50 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-1100H: molecular weight 800, number of functional groups 6) · Urethane acrylate B 10 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · Pentaerythritol triacrylate 40 parts (Toagosei Co., Ltd., trade name: M-305)
[0921] · 20 parts of silica particles (surface treated amorphous silica, d10: 1.2 μm, d50: 3.8 μm, d90: 6.5 μm) · 8 parts of organic particles A (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.515) · 2 parts of organic particles B (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.595) · 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[0922] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[0923] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[0924] Solvent (toluene) 190 parts
[0925] Solvent (cyclohexanone) 10 parts
[0926] Solvent (methyl isobutyl ketone) 15 parts
[0927] <Anti-glare layer coating liquid 1-5>
[0928] · Urethane acrylate A 50 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-1100H: molecular weight 800, number of functional groups 6) · Urethane acrylate B 10 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · Pentaerythritol triacrylate 40 parts (Toagosei Co., Ltd., trade name: M-305)
[0929] · Silica particles 10 parts (surface treated amorphous silica, d10: 1.0 μm, d50: 3.0 μm, d90: 4.8 μm) · Organic particles A 5 parts (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.515) · Organic particles B 5 parts (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.595) · Photopolymerization initiator 5.0 parts (IGM Resins BV, trade name: Omnirad184)
[0930] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[0931] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[0932] Solvent (toluene) 170 parts
[0933] Solvent (cyclohexanone) 40 parts
[0934] Solvent (methyl isobutyl ketone) 5 parts
[0935] <Anti-glare layer coating liquid 1-6>
[0936] 50 parts of polyurethane acrylate C (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[0937] 50 parts of pentaerythritol triacrylate (Toagosei Co., Ltd., trade name: M-305)
[0938] · Organic particles C 11 parts (spherical polyacrylic acid-styrene copolymer, average particle size 3.0 μm, refractive index 1.595) · Inorganic ultrafine particles 70 parts (silicon dioxide with reactive functional groups introduced on the surface, solvent: MIBK, solid content: 30%) (average primary particle size 12 nm)
[0939] 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[0940] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[0941] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[0942] Solvent (toluene) 170 parts
[0943] Solvent (cyclohexanone) 25 parts
[0944] <Anti-glare layer coating liquid 1-7>
[0945] · Urethane acrylate A 30 parts (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[0946] · 10 parts of polyurethane acrylate B (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · 60 parts of pentaerythritol triacrylate (Toagosei Co., Ltd., trade name: M-305)
[0947] · 3 parts of silica particles (surface treated amorphous silica, d10: 1.0 μm, d50: 3.0 μm, d90: 4.8 μm) · 0.5 parts of organic particles B (spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm, refractive index 1.595)
[0948] 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[0949] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[0950] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[0951] Solvent (toluene) 180 parts
[0952] Solvent (cyclohexanone) 5 parts
[0953] Solvent (methyl isobutyl ketone) 25 parts
[0954] <Low refractive index layer coating liquid 1-2>
[0955] ·Multifunctional acrylate 180 parts
[0956] (Toagosei Co., Ltd., trade name "Aronix M-400")
[0957] ·100 parts of hollow silica particles
[0958] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[0959] 600 parts of fluorine-based silicone leveling agent with reactive functional groups
[0960] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[0961] · Photopolymerization initiator 5 parts
[0962] (IGM Resins, product name: Omnirad127)
[0963] Solvent (methyl isobutyl ketone) 11,000 parts
[0964] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[0965] <Low refractive index layer coating liquid 1-3>
[0966] ·Multifunctional acrylate 100 parts
[0967] (Toagosei Co., Ltd., trade name "Aronix M-400")
[0968] ·100 parts of hollow silica particles
[0969] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[0970] 0.5 parts of acrylic polymer (weight average molecular weight: 40,000)
[0971] · 250 parts of fluorine-based silicone leveling agent with reactive functional groups
[0972] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[0973] · Photopolymerization initiator 5 parts
[0974] (IGM Resins, product name: Omnirad127)
[0975] Solvent (methyl isobutyl ketone) 11,000 parts
[0976] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[0977] <Low refractive index layer coating liquid 1-4>
[0978] ·Multifunctional acrylate 100 parts
[0979] (Toagosei Co., Ltd., trade name "Aronix M-400")
[0980] 0.5 parts of acrylic polymer (weight average molecular weight: 40,000)
[0981] ·180 parts of hollow silica particles
[0982] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[0983] 150 parts of fluorine-based silicone leveling agent with reactive functional groups
[0984] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[0985] · Photopolymerization initiator 5.0 parts
[0986] (IGM Resins, product name: Omnirad127)
[0987] Solvent (methyl isobutyl ketone) 11,000 parts
[0988] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[0989] [Table 1]
[0990]
[0991] [Table 2]
[0992]
[0993] From the results in Table 1, it can be confirmed that the optical film of the example of the first embodiment can achieve good anti-glare properties and fingerprint wiping properties.
[0994] 《Examples and Comparative Examples of the Second Embodiment》
[0995] 3. Measurement and evaluation
[0996] The optical films of the embodiments and comparative examples were measured and evaluated as follows. The atmosphere during each measurement and evaluation was: the temperature was 23±5°C, and the relative humidity was 40% to 65%. In addition, before each measurement and evaluation, the target sample was exposed to the atmosphere for 30 minutes to 60 minutes, and then the measurement and evaluation were performed. The results are shown in Table 3 or 4.
[0997] 3-1. Measurement of surface shape
[0998] The surface shapes of the optical films of Examples and Comparative Examples were measured by the same method as in 1-1 above.
[0999] 3-2. Contact angle
[1000] <Normal contact angle>
[1001] The normal contact angles of the optical films of Examples and Comparative Examples were measured by the same method as in 1-2 above.
[1002] <Falling contact angle>
[1003] A droplet with a surface tension of 30 mN / m was placed in a syringe whose needle was coated with fluororesin. For the first surface of each sample, a droplet with a surface tension of 30 mN / m was allowed to fall naturally from a height of 45 mm. The amount of the droplet that fell was 5.0 μl. Regarding the liquid, a liquid of the following composition was used. The droplet was allowed to fall from the vertical direction of the first surface. The static contact angle 10 seconds after landing was measured by the θ / 2 method. Regarding the measuring device, a contact angle meter (model: DM-300, Kyowa Interface Science Co., Ltd.) was used.
[1004] <Liquid composition>
[1005] This is a liquid containing 100% by mass of ethylene glycol monoethyl ether (Fujifilm Wako Pure Chemical Industries, Ltd., model: Mixed liquid for wetting tension test No. 30)
[1006] 3-3. Element ratio
[1007] The element ratios in the surface region of the first surface side of the optical films of Examples and Comparative Examples were measured by the same method as in 1-3 above.
[1008] 3-4. Total light reflectance (R SCI )
[1009] The total light reflectance (R SCI ).
[1010] 3-5. Haze (Hz)
[1011] The haze of the optical films of Examples and Comparative Examples was measured by the same method as in 1-5 above.
[1012] It should be noted that the total light transmittance of the optical films of Examples and Comparative Examples was 90% or more.
[1013] 3-6. Transmitted image clarity
[1014] The transmission image clarity of the optical films of Examples and Comparative Examples was measured by the same method as in 1-6 above.
[1015] 3-7. Black tone
[1016] The black tone of the optical films of Examples and Comparative Examples was evaluated by the same method as in 1-7 above.
[1017] 3-8. Anti-glare
[1018] The anti-glare properties of the optical films of Examples and Comparative Examples were evaluated by the same method as in 1-8 above.
[1019] 3-9. Fingerprint wipeability
[1020] The fingerprint wiping properties of the optical films of Examples and Comparative Examples were evaluated by the same method as in 1-9 above.
[1021] 3-10. Comprehensive evaluation
[1022] Comprehensive evaluation of the optical films of Examples and Comparative Examples was performed based on the same criteria as in 1 to 10 above.
[1023] 4. Production of optical films
[1024] [Example 2-1]
[1025] The following anti-glare coating liquid 2-1 was applied to a substrate (triacetyl cellulose resin film with a thickness of 80 μm, manufactured by Fujifilm Corporation). The film was then dried at 50° C. and a wind speed of 2 m / s for 40 seconds, and further dried at 70° C. and a wind speed of 15 m / s for 45 seconds. The film was then heated in a nitrogen atmosphere with an oxygen concentration of 200 ppm or less and the accumulated light intensity was 50 mJ / cm 2 The anti-glare layer with a thickness of 5.5 μm was formed by irradiating ultraviolet rays in a manner.
[1026] Next, the anti-glare layer was coated with the following low refractive index layer coating liquid 2-1. Next, it was dried at 40°C and a wind speed of 20 m / s for 15 seconds, and further dried at 70°C and a wind speed of 15 m / s for 30 seconds. Next, it was dried in a nitrogen atmosphere with an oxygen concentration of 200 ppm or less at a cumulative light intensity of 150 mJ / cm 2The low refractive index layer was irradiated with ultraviolet light in a manner of 0.10 μm thick to obtain an optical film of Example 2-1. The refractive index of the low refractive index layer was 1.31.
[1027] <Anti-glare layer coating liquid 2-1>
[1028] Polyurethane acrylate A 30 parts
[1029] (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[1030] · Polyurethane acrylate B 10 parts
[1031] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15)
[1032] · Pentaerythritol triacrylate 60 parts
[1033] (Toa Gosei Co., Ltd., trade name: M-305)
[1034] · 23 parts of silicon dioxide particles
[1035] (Surface treated amorphous silica, d10: 1.2μm, d50: 3.7μm, d90: 6.2μm)
[1036] · Organic particles B 8 parts
[1037] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5μm, refractive index 1.595)
[1038] · Photopolymerization initiator 5.0 parts
[1039] (IGM Resins BV, trade name: Omnirad184)
[1040] · Photopolymerization initiator 1.0 part
[1041] (IGM Resins BV, trade name: Omnirad907)
[1042] 0.1 part of silicone leveling agent
[1043] (Momentive Performance Materials, trade name: TSF 4460)
[1044] Solvent (toluene) 190 parts
[1045] Solvent (cyclohexanone) 5 parts
[1046] Solvent (methyl isobutyl ketone) 20 parts
[1047] <Low refractive index layer coating liquid 2-1>
[1048] ·Multifunctional acrylate 100 parts
[1049] (Toagosei Co., Ltd., trade name "Aronix M-400")
[1050] 0.5 parts of acrylic polymer (weight average molecular weight: 40,000)
[1051] ·180 parts of hollow silica particles
[1052] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[1053] 600 parts of fluorine-based silicone leveling agent with reactive functional groups
[1054] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[1055] · Photopolymerization initiator 5.0 parts
[1056] (IGM Resins, product name: Omnirad127)
[1057] Solvent (methyl isobutyl ketone) 11,000 parts
[1058] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[1059] [Examples 2-2, 2-3, 2-5, 2-6]
[1060] Optical films of Examples 2-2, 2-3, 2-5, and 2-6 were obtained in the same manner as in Example 2-1 except that the anti-glare layer coating liquid 2-1 was changed to the following anti-glare layer coating liquids 2-2 to 2-5.
[1061] [Examples 2-4]
[1062] An optical film of Example 2-4 was obtained in the same manner as in Example 2-1 except that the antiglare layer coating liquid 2-1 was changed to the following antiglare layer coating liquid 2-2 and the low refractive index layer coating liquid 2-1 was changed to the following low refractive index layer coating liquid 2-2.
[1063] [Example 2-7]
[1064] An optical film of Example 2-7 was obtained in the same manner as in Example 2-1 except that the anti-glare layer coating liquid 2-1 was changed to the following anti-glare layer coating liquid 2-6 and the thickness of the anti-glare layer was changed to 4.8 μm.
[1065] [Example 2-8]
[1066] An optical film of Example 2-8 was obtained in the same manner as in Example 2-1 except that the antiglare layer coating liquid 2-1 was changed to the following antiglare layer coating liquid 2-2 and the low refractive index layer coating liquid 2-1 was changed to the following low refractive index layer coating liquid 2-3. The refractive index of the low refractive index layer was 1.36.
[1067] [Comparative Example 2-1]
[1068] An optical film of Comparative Example 2-1 was obtained in the same manner as in Example 2-1 except that the low-refractive-index layer coating liquid 2-1 was changed to the following low-refractive-index layer coating liquid 2-4.
[1069] [Comparative Examples 2-2 to 2-3]
[1070] Optical films of Comparative Examples 2-2 to 2-3 were obtained in the same manner as in Comparative Example 2-1, except that the anti-glare layer coating liquid 2-1 was changed to the following anti-glare layer coating liquids 2-2 to 2-3.
[1071] [Comparative Examples 2-4]
[1072] An optical film of Comparative Example 2-4 was obtained in the same manner as in Example 2-1 except that the anti-glare layer coating liquid 2-1 was changed to the following anti-glare layer coating liquid 2-7 and the thickness of the anti-glare layer was changed to 5.0 μm.
[1073] <Anti-glare layer coating liquid 2-2>
[1074] Polyurethane acrylate A 30 parts
[1075] (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[1076] · Polyurethane acrylate B 10 parts
[1077] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15)
[1078] · Pentaerythritol triacrylate 60 parts
[1079] (Toa Gosei Co., Ltd., trade name: M-305)
[1080] · 21 parts of silicon dioxide particles
[1081] (Surface treated amorphous silica, d10: 1.2μm, d50: 3.7μm, d90: 6.2μm)
[1082] ·Organic particles B 10 parts
[1083] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5μm, refractive index 1.595)
[1084] · Photopolymerization initiator 5.0 parts
[1085] (IGM Resins BV, trade name: Omnirad184)
[1086] · Photopolymerization initiator 1.0 part
[1087] (IGM Resins BV, trade name: Omnirad907)
[1088] 0.1 part of silicone leveling agent
[1089] (Momentive Performance Materials, trade name: TSF 4460)
[1090] Solvent (toluene) 180 parts
[1091] Solvent (cyclohexanone) 15 parts
[1092] Solvent (methyl isobutyl ketone) 20 parts
[1093] <Anti-glare layer coating liquid 2-3>
[1094] Polyurethane acrylate A 30 parts
[1095] (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[1096] · Polyurethane acrylate B 10 parts
[1097] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) 60 parts of pentaerythritol triacrylate (Toagosei Co., Ltd., trade name: M-305)
[1098] · 19 parts of silica particles (surface treated amorphous silica, d10: 1.2 μm, d50: 3.7 μm, d90: 6.2 μm) · 3 parts of organic particles A (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.515) · 5 parts of organic particles B (spherical polyacrylic acid-styrene copolymer, average particle size of 1.5 μm, refractive index of 1.595) · 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[1099] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[1100] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[1101] Solvent (toluene) 175 parts
[1102] Solvent (cyclohexanone) 15 parts
[1103] Solvent (methyl isobutyl ketone) 25 parts
[1104] <Anti-glare layer coating liquid 2-4>
[1105] · Urethane acrylate A 30 parts (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[1106] · 10 parts of polyurethane acrylate B (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · 60 parts of pentaerythritol triacrylate (Toagosei Co., Ltd., trade name: M-305)
[1107] · 20 parts of silicon dioxide particles (surface treated amorphous silicon dioxide, d50: 3.5 μm)
[1108] · Organic particles A 8 parts (spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm, refractive index 1.515) · Organic particles B 2 parts (spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm, refractive index 1.595)
[1109] 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[1110] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[1111] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[1112] Solvent (toluene) 200 parts
[1113] Solvent (cyclohexanone) 5 parts
[1114] Solvent (methyl isobutyl ketone) 10 parts
[1115] <Anti-glare layer coating liquid 2-5>
[1116] · Urethane acrylate A 30 parts (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[1117] · 10 parts of polyurethane acrylate B (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · 60 parts of pentaerythritol triacrylate (Toagosei Co., Ltd., trade name: M-305)
[1118] · Silica particles 10 parts (surface treated amorphous silica, d10: 0.08 μm, d50: 2.8 μm, d90: 4.5 μm) · Organic particles A 5 parts (spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm, refractive index 1.515)
[1119] · Organic particles B 5 parts (spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm, refractive index 1.595)
[1120] 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[1121] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[1122] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[1123] Solvent (toluene) 180 parts
[1124] Solvent (cyclohexanone) 30 parts
[1125] Solvent (methyl isobutyl ketone) 5 parts
[1126] <Anti-glare layer coating liquid 2-6>
[1127] · Urethane acrylate C 60 parts (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-1100H: molecular weight 800, number of functional groups 6) · Pentaerythritol triacrylate 40 parts (Toagosei Co., Ltd., trade name: M-305)
[1128] · Organic particles C 11 parts (spherical polyacrylic acid-styrene copolymer, average particle size 3.0 μm, refractive index 1.595)
[1129] 70 parts of inorganic ultrafine particles (silicon dioxide with reactive functional groups introduced on the surface, solvent: MIBK, solid content: 30%) (average primary particle size: 12 nm)
[1130] 5.0 parts of photopolymerization initiator (IGM Resins BV, trade name: Omnirad184)
[1131] 1.0 part of photopolymerization initiator (IGM Resins BV, trade name: Omnirad907)
[1132] 0.1 part of silicone leveling agent (Momentive Performance Materials, trade name: TSF4460)
[1133] Solvent (toluene) 180 parts
[1134] Solvent (cyclohexanone) 15 parts
[1135] <Anti-glare layer coating liquid 2-7>
[1136] · Urethane acrylate A 30 parts (Mitsubishi Chemical Corporation, trade name: U-1700B: molecular weight 2000, number of functional groups 10)
[1137] · 10 parts of polyurethane acrylate B (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA: molecular weight 2300, number of functional groups 15) · 60 parts of pentaerythritol triacrylate (Toagosei Co., Ltd., trade name: M-305)
[1138] · 3 parts of silicon dioxide particles
[1139] (Surface treated amorphous silica, d10: 0.08μm, d50: 2.8μm, d90: 4.5μm)
[1140] ·Organic particles B 0.5 parts
[1141] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5μm, refractive index 1.595)
[1142] · Photopolymerization initiator 5.0 parts
[1143] (IGM Resins BV, trade name: Omnirad184)
[1144] · Photopolymerization initiator 1.0 part
[1145] (IGM Resins BV, trade name: Omnirad907)
[1146] 0.1 part of silicone leveling agent
[1147] (Momentive Performance Materials, trade name: TSF 4460)
[1148] Solvent (toluene) 180 parts
[1149] Solvent (cyclohexanone) 5 parts
[1150] Solvent (methyl isobutyl ketone) 25 parts
[1151] <Low refractive index layer coating liquid 2-2>
[1152] ·Multifunctional acrylate 180 parts
[1153] (Toagosei Co., Ltd., trade name "Aronix M-400")
[1154] ·100 parts of hollow silica particles
[1155] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[1156] 600 parts of fluorine-based silicone leveling agent with reactive functional groups
[1157] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[1158] · Photopolymerization initiator 5 parts
[1159] (IGM Resins, product name: Omnirad127)
[1160] Solvent (methyl isobutyl ketone) 11,000 parts
[1161] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[1162] <Low refractive index layer coating liquid 2-3>
[1163] ·Multifunctional acrylate 100 parts
[1164] (Toagosei Co., Ltd., trade name "Aronix M-400")
[1165] 0.5 parts of acrylic polymer (weight average molecular weight: 40,000)
[1166] ·100 parts of hollow silica particles
[1167] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[1168] · 250 parts of fluorine-based silicone leveling agent with reactive functional groups
[1169] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[1170] · Photopolymerization initiator 5 parts
[1171] (IGM Resins, product name: Omnirad127)
[1172] Solvent (methyl isobutyl ketone) 11,000 parts
[1173] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[1174] <Low refractive index layer coating liquid 2-4>
[1175] ·Multifunctional acrylate 100 parts
[1176] (Toagosei Co., Ltd., trade name "Aronix M-400")
[1177] 0.5 parts of acrylic polymer (weight average molecular weight: 40,000)
[1178] ·180 parts of hollow silica particles
[1179] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)
[1180] 150 parts of fluorine-based silicone leveling agent with reactive functional groups
[1181] (Shin-Etsu Chemical Co., Ltd., trade name "KY 1203", solid content: 20%, solvent: methyl isobutyl ketone)
[1182] · Photopolymerization initiator 5.0 parts
[1183] (IGM Resins, product name: Omnirad127)
[1184] Solvent (methyl isobutyl ketone) 11,000 parts
[1185] Solvent (1-methoxy-2-propyl acetate) 1300 parts
[1186] [Table 3]
[1187]
[1188] [Table 4]
[1189]
[1190] From the results of Table 3, it can be confirmed that the optical film of the example of the second embodiment can achieve good anti-glare properties and fingerprint wiping properties.
[1191] Description of symbols
[1192] 10: substrate;
[1193] 20: Anti-glare layer;
[1194] 30: anti-reflection layer;
[1195] 100: optical film;
[1196] 110: display element;
[1197] 120: image display panel;
[1198] 200: horizontal plane;
[1199] 300: the plane of the platform;
[1200] 400: Droplets.
Claims
1. An optical film comprising a first surface and a second surface which is a surface opposite to the first surface, wherein: The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface. The first surface has a concavoconvex shape, The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 Above and 0.100ml / m 2 Below, and the minimum autocorrelation length Sal of the first surface specified by ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less, The falling contact angle measured by the following method is 30.0 degrees or more, The drop contact angle is measured as follows: A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
2. The optical film according to claim 1, wherein The ratio (Vvv / Vvc) of Vvv of the first surface to the core space volume Vvc specified in ISO 25178-2:2012 is 0.10 or less.
3. The optical film according to claim 1 or 2, wherein: The minimum autocorrelation length Sal of the first surface specified in ISO 25178-2:2012 is 4.0 μm or more and 11.0 μm or less.
4. The optical film according to claim 1 or 2, wherein: The peak height Sxp of the first surface is not less than 0.15 μm and not more than 2.00 μm. The peak height Sxp is defined in ISO 25178-2:2012 and refers to the difference between a height at a load area ratio of 2.5% and a height at a load area ratio of 50%.
5. The optical film according to claim 1 or 2, wherein: The optical film includes the antireflection layer, the antiglare layer, and a substrate in this order from the first surface toward the second surface.
6. The optical film according to claim 1 or 2, wherein: The anti-glare layer includes a binder resin and particles.
7. The optical film according to claim 1 or 2, wherein: The element ratio of the optical film obtained by analyzing the surface region of the first surface side by X-ray photoelectron spectroscopy satisfies the following formulas 2 to 4: 3.5≤F / inorganic Si≤10.0 (Formula 2), 0.08≤Organic Si / Inorganic Si≤1.00 (Formula 3), 5.0≤F / organic Si≤50.0 (Formula 4), In Formulae 2 to 4, "F" is the ratio of fluorine element, "inorganic Si" is the ratio of silicon element belonging to inorganic silicon compound, and "organic Si" is the ratio of silicon element belonging to organic silicon compound.
8. The optical film according to claim 7, wherein: Regarding the element ratios analyzed by the X-ray photoelectron spectroscopy, the ratio of inorganic Si to all elements is 2 atomic % or more and 20 atomic % or less.
9. The optical film according to claim 1 or 2, wherein: The total light reflectance R of the optical film is measured by the following method SCI Below 3.0%, Total light reflectance R SCI The measurements are as follows: A sample was prepared by bonding a black plate to the second surface of the optical film via a transparent adhesive, and the total light reflectance R was measured with the optical film side of the sample as the light incident surface. SCI .
10. The optical film according to claim 1 or 2, wherein: The optical film has a haze of JIS K7136:2000 of 20% or more and 75% or less.
11. A polarizing plate comprising a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein: At least one of the first transparent protective plate and the second transparent protective plate is the optical film according to claim 1 or 2, and the second surface of the optical film is arranged to face the polarizer.
12. A surface plate for an image display device, which is formed by laminating a protective film on a resin plate or a glass plate, wherein: The protective film is the optical film according to claim 1 or 2, and the second surface of the optical film is disposed to face the resin plate or the glass plate.
13. An image display panel comprising a display element and an optical film disposed on a light emitting surface side of the display element, wherein: The image display panel includes the optical film according to claim 1 or 2 as the optical film.
14. An image display device, wherein: The image display device includes the image display panel according to claim 13.
15. A method for producing an optical film, which is the method for producing an optical film according to claim 1, wherein: The optical film production method includes: a first step of forming an anti-glare layer on a substrate; and a second step of forming an anti-reflection layer on the anti-glare layer.
16. A method for selecting an optical film, the method comprising selecting an optical film that satisfies the following selection conditions: The selection conditions of the optical film are as follows: The optical film has a first surface and a second surface which is a surface opposite to the first surface, wherein: The optical film has an antireflection layer and an antiglare layer in order from the first surface toward the second surface. The first surface has a concavoconvex shape, The protruding valley space volume Vvv of the first surface as specified in ISO 25178-2:2012 is 0.005 ml / m 2 Above and 0.100ml / m 2 Below, and the minimum autocorrelation length Sal of the first surface specified by ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less, The falling contact angle measured by the following method is 30.0 degrees or more, The drop contact angle is measured as follows: A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the first surface of the optical film in a direction perpendicular to the first surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
17. A method for evaluating fingerprint wipeability, wherein the value of the drop contact angle measured by the following measurement is used as an evaluation index, and when the drop contact angle is 30.0 degrees or more, the fingerprint wipeability is evaluated as good. The drop contact angle is measured as follows: A droplet having a surface tension of 30 mN / m was dropped from a height of 45 mm on the surface of the object to be measured, and the droplet was dropped perpendicularly to the surface, and the static contact angle 10 seconds after landing was measured by the θ / 2 method.
Citation Information
Patent Citations
Coat film
JP2019085473A
Anti-glare film
WO2019026466A1
Anti-glare film
WO2019026471A1
Optical film, polarizing plate, and image display apparatus
CN101398491A
Antiglare film, method for producing same, polarizing plate, image display device, member for touch panel
CN103582829A